A 17-kDa Fragment of Lactoferrin Associates With the Termination of Inflammation and Peptides Within Promote Resolution - Lutaty, Aviv; Soboh, Soaad; Schif-Zuck, Sagie; Zeituni-Timor, Orly; Rostoker, Ran; Podolska, Malgorzata; Herrmann, Martin; Munoz, Luis Enrique; Ariel, Amiram; Schauer, Christine (Frontiers in Immunology, 2018)
During the resolution of inflammation, macrophages engulf apoptotic polymorphonuclear cells (PMN) and can accumulate large numbers of their corpses. Here, we report that resolution phase macrophages acquire the neutrophil-derived glycoprotein lactoferrin (Lf) and fragments thereof in vivo and ex vivo. During the onset and resolving phases of inflammation in murine peritonitis and bovine mastitis, Lf fragments of 15 and 17 kDa occurred in various body fluids, and the murine fragmentation, accumulation, and release were mediated initially by neutrophils and later by efferocytic macrophages. The 17-kDa fragment contained two bioactive tripeptides, FKD and FKE that promoted resolution phase macrophage conversion to a pro-resolving phenotype. This resulted in a reduction in peritoneal macrophage numbers and an increase in the CD11b(low) subset of these cells. Moreover, FKE, but not FKD, peptides enhanced efferocytosis of apoptotic PMN, reduced TNF alpha and interleukin (IL)-6, and increased IL-10 secretion by lipopolysaccharide-stimulated macrophages ex vivo. In addition, FKE promoted neutrophil-mediated resolution at high concentrations (100 mu M) by enhancing the formation of cytokine-scavenging aggregated NETs (tophi) at a low cellular density. Thus, PMN Lf is processed, acquired, and "recycled" by neutrophils and macrophages during inflammation resolution to generate fragments and peptides with paramount pro-resolving activities.
EVALuna2:213271

A blast without power - cell death induced by the tuberculosis-necrotizing toxin fails to elicit adequate immune responses - Maueroeder, C.; Chaurio, R. A.; Dumych, T.; Podolska, M.; Lootsik, M. D.; Culemann, S.; Friedrich, Ralf P.; Bilyy, R.; Alexiou, Christoph; Schett, Georg; Berens, C.; Herrmann, Martin; et al. (Cell Death and Differentiation, 2016)
In this study, we deploy a doxycycline-dependent suicide switch integrated in a tumor challenge model. With this experimental setup, we characterized the immunological consequences of cells dying by four distinct cell death stimuli in vivo. We observed that apoptotic cell death induced by expression of the truncated form of BH3 interacting-domain death agonist (tBid) and a constitutively active form of caspase 3 (revC3), respectively, showed higher immunogenicity than cell death induced by expression of the tuberculosis-necrotizing toxin (TNT). Our data indicate that the early release of ATP induces the silent clearance of dying cells, whereas the simultaneous presence of 'find me' signals and danger-associated molecular patterns (DAMPs) promotes inflammatory reactions and increased immunogenicity. This proposed model is supported by findings showing that the production and release of high concentrations of IL-27 by bone-marrow-derived macrophages (BMDM) is limited to BMDM exposed to those forms of death that simultaneously released ATP and the DAMPs heat-shock protein 90 (HSP90) and high-mobility group box-1 protein (HMGB1). These results demonstrate that the tissue microenvironment generated by dying cells may determine the subsequent immune response.
EVALuna2:13264

Activation of liver X receptors inhibits experimental fibrosis by interfering with interleukin-6 release from macrophages - Beyer, Christian; Huang, Jingang; Beer, Juergen; Zhang, Yun; Palumbo-Zerr, Katrin; Zerr, Pawel; Distler, Alfiya; Dees, Clara; Maier, Christiane; Munoz, Louis; Krönke, Gerhard; Uderhardt, Stefan; et al. (Annals of the Rheumatic Diseases, 2015)
To investigate the role of liver X receptors (LXRs) in experimental skin fibrosis and evaluate their potential as novel antifibrotic targets.We studied the role of LXRs in bleomycin-induced skin fibrosis, in the model of sclerodermatous graft-versus-host disease (sclGvHD) and in tight skin-1 (Tsk-1) mice, reflecting different subtypes of fibrotic disease. We examined both LXR isoforms using LXR?-, LXR?- and LXR-?/?-double-knockout mice. Finally, we investigated the effects of LXRs on fibroblasts and macrophages to establish the antifibrotic mode of action of LXRs.LXR activation by the agonist T0901317 had antifibrotic effects in bleomycin-induced skin fibrosis, in the sclGvHD model and in Tsk-1 mice. The antifibrotic activity of LXRs was particularly prominent in the inflammation-driven bleomycin and sclGvHD models. LXR?-, LXR?- and LXR?/?-double-knockout mice showed a similar response to bleomycin as wildtype animals. Low levels of the LXR target gene ABCA-1 in the skin of bleomycin-challenged and control mice suggested a low baseline activation of the antifibrotic LXR signalling, which, however, could be specifically activated by T0901317. Fibroblasts were not the direct target cells of LXRs agonists, but LXR activation inhibited fibrosis by interfering with infiltration of macrophages and their release of the pro-fibrotic interleukin-6.We identified LXRs as novel targets for antifibrotic therapies, a yet unknown aspect of these nuclear receptors. Our data suggest that LXR activation might be particularly effective in patients with inflammatory disease subtypes. Activation of LXRs interfered with the release of interleukin-6 from macrophages and, thus, inhibited fibroblast activation and collagen release.
EVALuna2:12871

Active NET formation in Libman-Sacks endocarditis without antiphospholipid antibodies: A dramatic onset of systemic lupus erythematosus - Appelgren, Daniel; Dahle, Charlotte; Knopf, Jasmin; Bilyy, Rostyslav; Vovk, Volodymyr; Sundgren, Pia C.; Bengtsson, Anders A.; Wettero, Jonas; Munoz, Luis Enrique; Herrmann, Martin; Hoog, Anders; Sjowall, Christopher (Autoimmunity, 2018)
Although neutrophil extracellular traps (NETs) have been highlighted in several systemic inflammatory diseases, their clinical correlates and potential pathological role remain obscure. Herein, we describe a dramatic onset of systemic lupus erythematosus (SLE) with clear-cut pathogenic implications for neutrophils and NET formation in a young woman with cardiac (Libman-Sacks endocarditis) and central nervous system (psychosis and seizures) involvement. Despite extensive search, circulating antiphospholipid autoantibodies, a hallmark of Libman-Sacks endocarditis, could not be detected. Instead, we observed active NET formation in the tissue of the mitral valve, as well as in the circulation. Levels of NET remnants were significantly higher in serially obtained sera from the patient compared with sex-matched blood donors (p=.0011), and showed a non-significant but substantial correlation with blood neutrophil counts (r=0.65, p=.16). The specific neutrophil elastase activity measured in serum seemed to be modulated by the provided immunosuppressive treatment. In addition, we found anti-Ro60/SSA antibodies in the cerebrospinal fluid of the patient but not NET remnants or increased elastase activity. This case illustrates that different disease mechanisms mediated via autoantibodies can occur simultaneously in SLE. NET formation with release of cytotoxic NET remnants is a candidate player in the pathogenesis of this non-canonical form of Libman-Sacks endocarditis occurring in the absence of traditional antiphospholipid autoantibodies. The case description includes longitudinal results with clinical follow-up data and a discussion of the potential roles of NETs in SLE.
EVALuna2:213274

ADVANCES IN THE DETECTION OF PATHOGENIC AUTOANTIBODIES IN SLE - Munoz, Luis Enrique (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Aggregated NETs Sequester and Detoxify Extracellular Histones - Knopf, Jasmin; Leppkes, Moritz; Schett, Georg; Herrmann, Martin; Munoz, Luis Enrique (Frontiers in Immunology, 2019)
In response to various infectious and sterile stimuli neutrophils release chromatin decorated with bactericidal proteins, referred to as NETs. Their scaffolds are formed from chromatin fibers which display an apparent diameter of 15-17 nm and mainly consist from DNA (2 nm) and DNA-associated histones (11 nm). The NET-forming strands are thus not naked DNA but higher ordered chromatin structures. The histones may be released from the NET, especially if their tail arginines have been citrullinated. Several studies indicate that extracellular histones are toxic for mammalian epithelia and endothelia and contribute to the microvascular dysfunction observed e.g., in patients suffering from autoimmune diseases or sepsis. NETs formed at sites of very high neutrophil densities tend to clump and form fairly stable enzymatically active aggregates, referred to as aggNETs. The latter are endowed with a bunch of enzymes that cleave, bind, and/or modify autologous as well as foreign macromolecules. The tight binding of the serine proteases to the matrix precludes the spread of these toxic enzymes into the tissue but still allows the access of soluble inflammatory mediators to the enzymatic active internal surfaces of the NETs where they are degraded. Here, we describe that externally added histones are removed from culture supernatants of aggNETs. We will address the fate of the histones and discuss the feature on the background of neutrophil-driven diseases and the resolution of inflammation.
CRIS-Team WoS Importer:2019-09-24

Aggregated neutrophil extracellular traps limit inflammation by degrading cytokines and chemokines - Schauer, Christine; Janko, Christina; Munoz Becerra, Luis; Zhao, Yi; Kienhöfer, Deborah; Frey, Benjamin; Lell, Michael; Manger, Bernhard; Rech, Juergen; Naschberger, Elisabeth; Holmdahl, Rikard; Krenn, Veit; et al. (Nature Medicine, 2014)
Gout is characterized by an acute inflammatory reaction and the accumulation of neutrophils in response to monosodium urate (MSU) crystals. Inflammation resolves spontaneously within a few days, although MSU crystals can still be detected in the synovial fluid and affected tissues. Here we report that neutrophils recruited to sites of inflammation undergo oxidative burst and form neutrophil extracellular traps (NETs). Under high neutrophil densities, these NETs aggregate and degrade cytokines and chemokines via serine proteases. Tophi, the pathognomonic structures of chronic gout, share characteristics with aggregated NETs, and MSU crystals can induce NETosis and aggregation of NETs. In individuals with impaired NETosis, MSU crystals induce uncontrolled production of inflammatory mediators from neutrophils and persistent inflammation. Furthermore, in models of neutrophilic inflammation, NETosis-deficient mice develop exacerbated and chronic disease that can be reduced by adoptive transfer of aggregated NETs. These findings suggest that aggregated NETs promote the resolution of neutrophilic inflammation by degrading cytokines and chemokines and disrupting neutrophil recruitment and activation.
Created from Fastlane, Scopus look-up

Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

Alpha-1 antitrypsin in autoimmune diseases: Roles and therapeutic prospects - Sun, Rui; Xu, Zhiqiang; Zhu, Chenxi; Chen, Tao; Munoz, Luis Enrique; Dai, Lunzhi; Zhao, Yi (International Immunopharmacology, 2022)
Alpha-1 antitrypsin (A1AT) is a protease inhibitor in the serum. Its primary function is to inhibit the activity of a series of proteases, including proteinase 3, neutrophil elastase, metalloproteases, and cysteine-aspartate proteases. In addition, A1AT also has anti-inflammatory, anti-apoptotic, anti-oxidative stress, anti-viral, and antibacterial activities and plays essential roles in the regulation of tissue repair and lymphocyte differentiation and activation. The overactivation of the immune system characterizes the pathogenesis of autoimmune diseases. A1AT treatment shows beneficial effects on patients and animal models with autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. This review summarizes the functions and therapeutic prospects of A1AT in autoimmune diseases.
CRIS-Team WoS Importer:2022-07-29

Altered glycan accessibility on native immunoglobulin G complexes in early rheumatoid arthritis and its changes during therapy - Stuemer, J.; Biermann, Mona; Knopf, Jasmin; Magorivska, I.; Kastbom, A.; Svaerd, A.; Janko, Christina; Bilyy, R.; Schett, Georg; Sjoewall, C.; Herrmann, Martin; Munoz, Luis Enrique; et al. (Clinical and Experimental Immunology, 2017)
The goal of this study was to investigate the glycosylation profile of native immunoglobulin (Ig)G present in serum immune complexes in patients with rheumatoid arthritis (RA). To accomplish this, lectin binding assays, detecting the accessibility of glycans present on IgG-containing immune complexes by biotinylated lectins, were employed. Lectins capturing fucosyl residues (AAL), fucosylated tri-mannose N-glycan core sites (LCA), terminal sialic acid residues (SNA) and O-glycosidically linked galactose/N-acetylgalactosamine (GalNac-L) were used. Patients with recent-onset RA at baseline and after 3-year follow-up were investigated. We found that native IgG was complexed significantly more often with IgM, C1q, C3c and C-reactive protein (CRP) in RA patients, suggesting alterations of the native structure of IgG. The total accessibility of fucose residues on captured immune complexes to the respective lectin was significantly higher in patients with RA. Moreover, fucose accessibility on IgG-containing immune complexes correlated positively with the levels of antibodies to cyclic citrullinated peptides (anti-CCP). We also observed a significantly higher accessibility to sialic acid residues and galactose/GalNAc glyco-epitopes in native complexed IgG of patients with RA at baseline. While sialic acid accessibility increased during treatment, the accessibility of galactose/GalNAc decreased. Hence, successful treatment of RA was associated with an increase in the SNA/GalNAc-L ratio. Interestingly, the SNA/GalNAc-L ratio in particular rises after glucocorticoid treatment. In summary, this study shows the exposure of glycans in native complexed IgG of patients with early RA, revealing particular glycosylation patterns and its changes following pharmaceutical treatment.
EVALuna2:13418

Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus - Sjowall, Christopher; Zapf, J.; Von Loehneysen, S.; Magorivska, I.; Biermann, M.; Janko, Christina; Winkler, Sophie; Bilyy, R.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2015)
In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of well-characterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during periods of increased disease activity and remission were analysed. All patients fulfilled the 1982 American College of Rheumatology classification criteria. Sera of 15 sex- and age-matched normal healthy blood donors served as controls. The levels and type of glycosylation of complexed random IgG was measured with lectin enzyme-immunosorbent assays. After specifically gathering IgG complexes from sera, biotinylated lectins Aleuria aurantia lectin and Lens culinaris agglutinin were employed to detect IgG-associated fucosyl residues and the fucosylated tri-mannose N-glycan core, respectively. In sandwich-ELISAs, IgG-associated IgM, IgA, C1q, C3c and C-reactive protein (CRP) were detected as candidates for IgG immune complex constituents. We studied associations of the glycan of complexed IgG and disease activity according to the physician's global assessment of disease activity and the systemic lupus erythematosus disease activity index 2000 documented at the moment of blood taking. Our results showed significantly higher levels of Aleuria aurantia lectin and Lens culinaris agglutinin binding sites exposed on IgG complexes of patients with systemic lupus erythematosus than on those of normal healthy blood donors. Disease activity in systemic lupus erythematosus correlated with higher exposure of Aleuria aurantia lectin-reactive fucosyl residues by immobilized IgG complexes. Top levels of Aleuria aurantia lectin-reactivity were found in samples taken during the highest activity of systemic lupus erythematosus. Our results show that native circulating IgG complexes from active systemic lupus erythematosus patients expose fucosyl residues and their glycan core is accessible to soluble lectins. Two putative mechanisms may contribute to the increased exposure of these glycans: (1) the canonical N-glycosylation site of the IgG-CH2 domain; (2) an IgG binding non-IgG molecule, like complement or C-reactive protein. In both cases the complexed IgG may be alternatively targeted to lectin receptors of effector cells, e.g. dendritic cells.
EVALuna2:13017

Annexin A5 regulates surface αvβ5 integrin for retinal clearance phagocytosis - Yu, Chen; Munoz Becerra, Luis; Mallavarapu, Mallika; Herrmann, Martin; Finnemann, Silvia C. (Journal of cell science, 2019)
Diurnal clearance phagocytosis by the retinal pigment epithelium (RPE) is a conserved efferocytosis process whose binding step is mediated by αvβ5 integrin receptors. Two related annexins, A5 (ANXA5) and A6 (ANXA6), share an αvβ5 integrin-binding motif. Here, we report that ANXA5, but not ANXA6, regulates the binding capacity for spent photoreceptor outer segment fragments or apoptotic cells by fibroblasts and RPE. Similar to αvβ5-deficient RPE, ANXA5-/- RPE in vivo lacks the diurnal burst of phagocytosis that follows photoreceptor shedding in wild-type retina. Increasing ANXA5 in cells lacking αvβ5 or increasing αvβ5 in cells lacking ANXA5 does not affect particle binding. Association of cytosolic ANXA5 and αvβ5 integrin in RPE in culture and in vivo further supports their functional interdependence. Silencing ANXA5 is sufficient to reduce levels of αvβ5 receptors at the apical phagocytic surface of RPE cells. The effect of ANXA5 on surface αvβ5 and on particle binding requires the C-terminal ANXA5 annexin repeat but not its unique N-terminus. These results identify a novel role for ANXA5 specifically in the recognition and binding step of clearance phagocytosis, which is essential to retinal physiology.This article has an associated First Person interview with the first author of the paper.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Annexin A5; Clearance phagocytosis; Efferocytosis; Integrin; Retina; RPE

Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

Anti-DNA-IgM Favors the Detection of NET-Associated Extracellular DNA - Wang, Han; Stehr, Antonia; Singh, Jeeshan; Zlatar, Leticija; Hartmann, Arndt; Evert, Katja; Naschberger, Elisabeth; Von Stillfried, Saskia; Boor, Peter; Munoz, Luis Enrique; Knopf, Jasmin; Stürzl, Michael; et al. (International Journal of Molecular Sciences, 2023)
During inflammatory responses, neutrophils enter the sites of attack where they execute various defense mechanisms. They (I) phagocytose microorganisms, (II) degranulate to release cytokines, (III) recruit various immune cells by cell-type specific chemokines, (IV) secrete anti-microbials including lactoferrin, lysozyme, defensins and reactive oxygen species, and (V) release DNA as neutrophil extracellular traps (NETs). The latter originates from mitochondria as well as from decondensed nuclei. This is easily detected in cultured cells by staining of DNA with specific dyes. However, in tissues sections the very high fluorescence signals emitted from the condensed nuclear DNA hamper the detection of the widespread, extranuclear DNA of the NETs. In contrast, when we employ anti-DNA-IgM antibodies, they are unable to penetrate deep into the tightly packed DNA of the nucleus, and we observe a robust signal for the extended DNA patches of the NETs. To validate anti-DNA-IgM, we additionally stained the sections for the NET-markers histone H2B, myeloperoxidase, citrullinated histone H3, and neutrophil elastase. Altogether, we have described a fast one-step procedure for the detection of NETs in tissue sections, which provides new perspectives to characterize neutrophil-associated immune reactions in disease.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-DNA-IgM; extracellular DNA; NETs

A Pleomorphic Puzzle: Heterogeneous Pulmonary Vascular Occlusions in Patients with COVID-19 - Singh, Jeeshan; Herrmann, Irmgard; Mahajan, Aparna; Schauer, Christine; Shan, Xiaomei; Hartmann, Arndt; Rieker, Ralf; Evert, Katja; Falkeis, Christina; Naschberger, Elisabeth; von Stillfried, Saskia; Boor, Peter; et al. (International Journal of Molecular Sciences, 2022)
Vascular occlusions in patients with coronavirus diseases 2019 (COVID-19) have been frequently reported in severe outcomes mainly due to a dysregulation of neutrophils mediating neutrophil extracellular trap (NET) formation. Lung specimens from patients with COVID-19 have previously shown a dynamic morphology, categorized into three types of pleomorphic occurrence based on histological findings in this study. These vascular occlusions in lung specimens were also detected using native endogenous fluorescence or NEF in a label-free method. The three types of vascular occlusions exhibit morphology of DNA rich neutrophil elastase (NE) poor (type I), NE rich DNA poor (type II), and DNA and NE rich (type III) cohort of eleven patients with six males and five females. Age and gender have been presented in this study as influencing variables linking the occurrence of several occlusions with pleomorphic contents within a patient specimen and amongst them. This study reports the categorization of pleomorphic occlusions in patients with COVID-19 and the detection of these occlusions in a label-free method utilizing NEF.
CRIS-Team Scopus Importer:2022-12-23
Keywords: age; COVID-19; gender; immunothrombosis; native endogenous fluorescence; occlusions; pleomorphism; SARS-CoV-2

Apoptotic cell clearance and its role in the origin and resolution of chronic inflammation - Munoz, Luis Enrique; Berens, Christian; Lauber, Kirsten; Gaipl, Udo; Herrmann, Martin (Frontiers in Immunology, 2015)
EVALuna2:13110

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

Autoantibodies Activating the β2-Adrenergic Receptor Characterize Patients With Primary and Secondary Glaucoma - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Kara, Katja; Mardin, Christian Y.; Lämmer, Robert; Schlötzer-Schrehardt, Ursula; Hosari, Sami; Horn, Folkert; Munoz Becerra, Luis; Herrmann, Martin (Frontiers in Immunology, 2019)
Recently, agonistic autoantibodies (agAAb) activating the β2-adrenergic receptor were detected in primary open-angle glaucoma (POAG) or ocular hypertension (OHT) patients and were linked to intraocular pressure (IOP) (1). The aim of the present study was to quantify β2-agAAb in the sera of glaucoma suspects and patients with primary and secondary glaucoma. Patients with OHT (n = 33), pre-perimetric POAG (pre-POAG; n = 11), POAG (n = 28), and 11 secondary OAG (SOAG) underwent ophthalmological examinations including examinations with Octopus G1 perimetry and morphometry. Twenty-five healthy individuals served as controls. Serum-derived IgG samples were analyzed for β2-agAAb using a functional bioassay. The beat-rate-increase of spontaneously beating cultured neonatal rat cardiomyocytes was monitored with 1.6 beats/15 s as cut-off. None of the sera of normal subjects showed β2-agAAb. In POAG or OHT patients increased beating rates of 4.1 ± 2.2 beats/15 s, and 3.7 ± 2.8 beats/15 s were detected (p > 0.05). Glaucoma patients with (POAG) and without perimetric (pre-POAG) defects did not differ (pre-POAG 4.4 ± 2.6 beats/15 s, POAG 4.1 ± 2.0 beats/15 s, p > 0.05). Patients with SOAG yielded mean beating rates of 4.7 ± 1.7 beats/15 s (p > 0.05). β2-agAAb were seen in 73% of OHT, 82% of pre-POAG, 82% of POAG, and 91% SOAG patients (p < 0.001). Clinical data did not correlate with beating rate (p > 0.05). The robust β2-agAAb seropositivity in patients with OHT, pre-POAG, POAG, and SOAG suggest a primary common role for β2-agAAb starting early in glaucoma pathophysiology and turned out to be a novel marker identifying all patients with increased IOP independent of glaucoma stage and entity.
CRIS-Team Scopus Importer:2019-10-29
Keywords: autoantibodies; glaucoma; ocular hypertension; primary open-angle glaucoma; secondary open-angle glaucoma; β2-adrenergic receptor

Autoantibodies against galectins are associated with antiphospholipid syndrome in patients with systemic lupus erythematosus - Sarter, Kerstin; Janko, Christina; Andre, Sabine; Munoz, Luis Enrique; Schorn, Christine; Winkler, Sophie; Rech, Jürgen; Kaltner, Herbert; Lorenz, Hanns-Martin; Schiller, Martin; Andreoli, Laura; Manfredi, Angelo A.; et al. (Glycobiology, 2013)
The presence of autoantibodies against immunoregulatory effectors can be relevant for onset and/or the progression of autoimmune disease. Emerging insights into an immunological activity profile including a role as opsonins give reason to systematically monitor sera of patients for immunoglobulin G (IgG) autoantibodies, preferably for several galectins at the same time. Here, we report on a study of chronic inflammatory rheumatic diseases, i.e. systemic lupus erythematosus (SLE; pilot cohort p, n = 40; confirmation cohort c, n = 109), rheumatoid arthritis (RA; p, n = 32; c, n = 25) and primary antiphospholipid syndrome (APS; c, n = 64). Enzyme-linked immunosorbent assay-based series using galectin-1, -2, -3, -4, -7, -8 and -9 and natural processing products, i.e. the truncated version of galectin-3 and the N-terminal domains of galectin-4, -8 and -9, were performed. Normal healthy donors (p, n = 20; c, n = 21) and patients with paraproteins (c, n = 19) served as controls. Highly significant optical density-value readings for IgG autoantibodies were consistently detected for the proto-type galectin-7 (SLE) and the tandem repeat-type galectin-8 and -9 (SLE and RA). Their presence was independent from the autoantibody status against double-stranded DNA (for patients with SLE) or a rheumatoid factor (for patients with RA), respectively. Importantly, anti-galectin-2 autoantibodies highly significantly correlated with the appearance of a secondary APS in patients with SLE so that this parameter may serve as an additional biomarker for APS. Equally of note, the presence of IgG autoantibodies against galectins capable to act as an opsonin may contribute to a sustained immune dysregulation in patients with chronic inflammatory rheumatic diseases. © The Author 2012. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2021-02-03
Keywords: antiphospholipid syndrome; autoantibodies; galectins; systemic lupus erythematosus

Autoantibodies Recognizing Secondary NEcrotic Cells Promote Neutrophilic Phagocytosis and Identify Patients With Systemic Lupus Erythematosus - Biermann, Mona; Boeltz, Sebastian; Pieterse, Elmar; Knopf, Jasmin; Rech, Jürgen; Bilyy, Rostyslav; Van Der Vlag, Johan; Tincani, Angela; Distler, Jörg; Krönke, Gerhard; Schett, Georg; Herrmann, Martin; et al. (Frontiers in Immunology, 2018)
Deficient clearance of apoptotic cells reportedly contributes to the etiopathogenesis of the autoimmune disease systemic lupus erythematosus (SLE). Based on this knowledge, we developed a highly specific and sensitive test for the detection of SLE autoantibodies (AAb) utilizing secondary NEcrotic cell (SNEC)-derived material as a substrate. The goal of the present study was to validate the use of SNEC as an appropriate antigen for the diagnosis of SLE in large cohort of patients. We confirmed the presence of apoptotically modified autoantigens on SNEC (dsDNA, high mobility group box 1 protein, apoptosis-associated chromatin modifications, e.g., histones H3-K27-me3; H2A/H4 AcK8,12,16; and H2B-AcK12). Anti-SNEC AAb were measured in the serum of 155 patients with SLE, 89 normal healthy donors (NHD), and 169 patients with other autoimmune connective tissue diseases employing SNEC-based indirect enzyme-linked immunosorbent assay (SNEC ELISA). We compared the test performance of SNEC ELISA with the routine diagnostic tests dsDNA Farr radioimmunoassay (RIA) and nucleosome-based ELISA (anti-dsDNA-NcX-ELISA). SNEC ELISA distinguished patients with SLE with a specificity of 98.9% and a sensitivity of 70.6% from NHD clearly surpassing RIA and anti-dsDNA-NcX-ELISA. In contrast to the other tests, SNEC ELISA significantly discriminated patients with SLE from patients with rheumatoid arthritis, primary anti-phospholipid syndrome, spondyloarthropathy, psoriatic arthritis, and systemic sclerosis. A positive test result in SNEC ELISA significantly correlated with serological variables and reflected the uptake of opsonized SNEC by neutrophils. This stresses the relevance of SNECs in the pathogenesis of SLE. We conclude that SNEC ELISA allows for the sensitive detection of pathologically relevant AAb, enabling its diagnostic usage. A positive SNEC test reflects the opsonization of cell remnants by AAb, the neutrophil recruitment to tissues, and the enhancement of local and systemic inflammatory responses.
EVALuna2:34144

Autoimmune, rheumatic, chronic inflammatory diseases: Neutrophil extracellular traps on parade - Podolska, Malgorzata; Mahajan, Aparna; Knopf, Jasmin; Hahn, Jonas; Boeltz, Sebastian; Munoz, Luis Enrique; Bilyy, Rostyslav; Herrmann, Martin (Autoimmunity, 2018)
Rheumatic diseases are a group of inflammatory conditions that affect joints and connective tissues and are often accompanied by pain and restriction of motility. In many of these diseases, autoantibodies develop that react with molecules/structures commonly found hidden in neutrophils. Neutrophil extracellular trap (NET) formation and release is considered a defense mechanism against pathogens or endogenous danger signals and it has been associated with initial inflammatory responses. NETs are also endowed with an important resolution potential based on its intrinsic enzymatic activity, but in the case they are not timely removed from the crime scene they might modulate subsequent immune responses and contribute to the pathogenesis of chronic inflammatory diseases. In this review, we will summarize the actual knowledge about the multifaceted roles of NETs in the etiology and pathogenesis of rheumatic autoimmune diseases.
EVALuna2:34670

Autoimmune, rheumatic, chronic inflammatory diseases: Neutrophil extracellular traps on parade - Podolska, Malgorzata; Mahajan, Aparna; Knopf, Jasmin; Hahn, Jonas; Boeltz, Sebastian; Munoz, Luis Enrique; Bilyy, Rostyslav; Herrmann, Martin (Autoimmunity Reviews, 2018)
Keywords: Neutrophil extracellular traps; rheumatic diseases; antiphospholipid syndrome; rheumatoid arthritis; systemic lupus erythematosus

Autophagy regulates TNFα-mediated joint destruction in experimental arthritis - Lin, Neng-Yu; Beyer, Christian; Gießl, Andreas; Kireva, Trayana; Scholtysek, Carina; Uderhardt, Stefan; Munoz, Luis Enrique; Dees, Clara; Distler, Alfiya; Wirtz, Stefan; Krönke, Gerhard; Spencer, Brian; et al. (Annals of the Rheumatic Diseases, 2013)
Objectives: Autophagy is a homeostatic process to recycle dispensable and damaged cell organelles. Dysregulation of autophagic pathways has recently been implicated in the pathogenesis of various diseases. Here, we investigated the role of autophagy during joint destruction in arthritis. Methods: Autophagy in osteoclasts was analysed in vitro and ex vivo by transmission electron microscopy, Western blotting and immunohistochemistry for Beclin1 and Atg7. Small molecule inhibitors, LysMCre-mediated knockout of Atg7 and lentiviral overexpression of Beclin1 were used to modulate autophagy in vitro and in vivo. Osteoclast differentiation markers were quantified by realtime PCR. The extent of bone and cartilage destruction was analysed in human tumour necrosis factor α transgenic (hTNFα tg) mice after adoptive transfer with myeloid specific Atg7-deficient bone marrow. Results: Autophagy was activated in osteoclasts of human rheumatoid arthritis (RA) showing increased expression of Beclin1 and Atg7. TNFα potently induced the expression of autophagy-related genes and activated autophagy in vitro and in vivo. Activation of autophagy by overexpression of Beclin1-induced osteoclastogenesis and enhanced the resorptive capacity of cultured osteoclasts, whereas pharmacologic or genetic inactivation of autophagy prevented osteoclast differentiation. Arthritic hTNFα tg mice transplanted with Atg7fl/fl×LysMCre+ bone marrow cells (BMC) showed reduced numbers of osteoclasts and were protected from TNFα-induced bone erosion, proteoglycan loss and chondrocyte death. Conclusions: These findings demonstrate that autophagy is activated in RA in a TNFα-dependent manner and regulates osteoclast differentiation and bone resorption. We thus provide evidence for a central role of autophagy in joint destruction in RA.
CRIS-Team Scopus Importer:2020-11-20

Blood-borne phagocytes internalize urate microaggregates and prevent intravascular NETosis by urate crystals - Pieterse, Elmar; Jeremic, Ivica; Czegley, Christine; Weidner, Daniela; Biermann, Mona; Veissi, Susan; Maueröder, Christian; Schauer, Christine; Bilyy, Rostyslav; Dumych, Tetiana; Hoffmann, Markus; Munoz, Luis Enrique; et al. (Scientific Reports, 2016)
Hyperuricemia is strongly linked to cardiovascular complications including atherosclerosis and thrombosis. In individuals with hyperuricemia, needle-shaped monosodium urate crystals (nsMSU) frequently form within joints or urine, giving rise to gouty arthritis or renal calculi, respectively. These nsMSU are potent instigators of neutrophil extracellular trap (NET) formation. Little is known on the mechanism(s) that prevent nsMSU formation within hyperuricemic blood, which would potentially cause detrimental consequences for the host. Here, we report that complement proteins and fetuins facilitate the continuous clearance by blood-borne phagocytes and resident macrophages of small urate microaggregates (UMA; <1 ?m in size) that initially form in hyperuricemic blood. If this clearance fails, UMA exhibit bipolar growth to form typical full-sized nsMSU with a size up to 100 ?m. In contrast to UMA, nsMSU stimulated neutrophils to release NETs. Under conditions of flow, nsMSU and NETs formed densely packed DNase I-resistant tophus-like structures with a high obstructive potential, highlighting the importance of an adequate and rapid removal of UMA from the circulation. Under pathological conditions, intravascularly formed nsMSU may hold the key to the incompletely understood association between NET-driven cardiovascular disease and hyperuricemia.
EVALuna2:13377

Butyrophilin 2a2 (Btn2a2) expression on thymic epithelial cells promotes central T cell tolerance and prevents autoimmune disease: Btn2a2 promotes central tolerance - Frech, Michael; Danzer, Heike; Uchil, Pooja; Azizov, Vugar; Schmid, Eva; Schälter, Fabian; Dürholz, Kerstin; Mauro, Daniele; Rauber, Simon; Munoz Becerra, Luis; Taher, Leila; Ciccia, Francesco; et al. (Journal of Autoimmunity, 2023)
Butyrophilins are surface receptors belonging to the immunoglobulin superfamily. While several members of the butyrophilin family have been implicated in the development of unconventional T cells, butyrophilin 2a2 (Btn2a2) has been shown to inhibit conventional T cell activation. Here, we demonstrate that in steady state, the primary source of Btn2a2 are thymic epithelial cells (TEC). Absence of Btn2a2 alters thymic T cell maturation and bypasses central tolerance mechanisms. Furthermore, Btn2a2−/− mice develop spontaneous autoimmunity resembling human primary Sjögren's Syndrome (pSS), including formation of tertiary lymphoid structures (TLS) in target organs. Ligation of Btn2a2 on developing thymocytes is associated with reduced TCR signaling and CD5 levels, while absence of Btn2a2 results in increased TCR signaling and CD5 levels. These results define a novel role for Btn2a2 in promoting central tolerance by modulating TCR signaling strength and indicate a potential mechanism of pSS development.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune disease; Autoimmunity; Butyrophilin 2a2 (Btn2a2); Central tolerance; Primary sjögren's syndrome (pSS); Thymic epithelial cells (TEC)

Calpain-1 weakens the nuclear envelope and promotes the release of neutrophil extracellular traps - Singh, Jeeshan; Zlatar, Leticija; Munoz Becerra, Marco; Lochnit, Günter; Herrmann, Irmgard; Pfister, Felix; Janko, Christina; Knopf, Jasmin; Leppkes, Moritz; Schoen, Janina; Munoz, Luis Enrique; Schett, Georg; et al. (Cell Communication and Signaling, 2024)
The inducers of neutrophil extracellular trap (NET) formation are heterogeneous and consequently, there is no specific pathway or signature molecule indispensable for NET formation. But certain events such as histone modification, chromatin decondensation, nuclear envelope breakdown, and NET release are ubiquitous. During NET formation, neutrophils drastically rearrange their cytoplasmic, granular and nuclear content. Yet, the exact mechanism for decoding each step during NET formation still remains elusive. Here, we investigated the mechanism of nuclear envelope breakdown during NET formation. Immunofluorescence microscopic evaluation revealed a gradual disintegration of outer nuclear membrane protein nesprin-1 and alterations in nuclear morphology during NET formation. MALDI-TOF analysis of NETs that had been generated by various inducers detected the accumulation of nesprin-1 fragments. This suggests that nesprin-1 degradation occurs before NET release. In the presence of a calpain-1, inhibitor nesprin-1 degradation was decreased in calcium driven NET formation. Microscopic evaluation confirmed that the disintegration of the lamin B receptor (LBR) and the collapse of the actin cytoskeleton occurs in early and later phases of NET release, respectively. We conclude that the calpain-1 degrades nesprin-1, orchestrates the weakening of the nuclear membrane, contributes to LBR disintegration, and promoting DNA release and finally, NETs formation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Calpain-1; Nesprin-1; Neutrophil extracellular traps (NETs); Nuclear envelope break down

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

Cerebrospinal Fluid of Patients With Alzheimer's Disease Contains Increased Percentages of Synaptophysin-Bearing Microvesicles - Utz, Janine; Berner, Judith; Munoz, Luis Enrique; Oberstein, Timo; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel; Spitzer, Philipp (Frontiers in Aging Neuroscience, 2021)
Introduction In Alzheimer's disease, the severity of symptoms is linked to a loss of synaptic density and the spread of pathologically hyperphosphorylated tau. The established cerebrospinal fluid markers A beta, tau and phospho-tau reflect the histopathological hallmarks of Alzheimer's disease but do not indicate disease progression. Such markers are of special interest, especially for trials of disease modifying drugs. Microvesicles are produced by stressed cells and reflect part of the metabolism of their cells of origin. Therefore, we investigated microvesicles of neuronal origin in cerebrospinal fluid. Materials and Methods We used flow cytometry to analyze microvesicles carrying tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, synaptophysin, and SNAP-25 in the cerebrospinal fluid of 19 patients with Alzheimer's disease and 15 non-inflammatory neurological disease controls. Results The percentages of synaptophysin-bearing microvesicles were significantly higher in the cerebrospinal fluid of patients with Alzheimer's disease than in the CSF of non-inflammatory neurological disease controls. Tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, and SNAP-25 did not differ between the groups. The percentages of synaptophysin-bearing vesicles distinguished patients with Alzheimer's disease from the controls (AUC = 0.81). Conclusion The loss of synapses in Alzheimer's disease may be reflected by synaptophysin-bearing microvesicles in the cerebrospinal fluid. Future studies are needed to investigate the possibility of using these MVs as a marker to determine the activity of Alzheimer's disease.
CRIS-Team WoS Importer:2021-07-30

Chemical Tools for Targeted Amplification of Reactive Oxygen Species in Neutrophils - Reshetnikov, Viktor; Hahn, Jonas; Maueroeder, Christian; Czegley, Christine; Munoz, Luis Enrique; Herrmann, Martin; Hoffmann, Markus; Mokhir, Andriy (Frontiers in Immunology, 2018)
A number of chemical compounds are known, which amplify the availability of reactive oxygen species (ROS) in neutrophils both in vitro and in vivo. They can be roughly classified into NADPH oxidase 2 (NOX2)-dependent and NOX2-independent reagents. NOX2 activation is triggered by protein kinase C agonists (e.g., phorbol esters, transition metal ions), redox mediators (e.g., paraquat) or formyl peptide receptor (FPR) agonists (e.g., aromatic hydrazine derivatives). NOX2-independent mechanisms are realized by reagents affecting glutathione homeostasis (e.g., L-buthionine sulfoximine), modulators of the mitochondrial respiratory chain (e.g., ionophores, inositol mimics, and agonists of peroxisome proliferator-activated receptor gamma) and chemical ROS amplifiers [e.g., aminoferrocene-based prodrugs (ABPs)]. Since a number of inflammatory and autoimmune diseases, as well as cancer and bacterial infections, are triggered or enhanced by aberrant ROS production in neutrophils, it is tempting to use ROS amplifiers as drugs for the treatment of these diseases. However, since the known reagents are not cell specific, their application for treatment likely causes systemic enhancement of oxidative stress, leading to severe side effects. Cell-targeted ROS enhancement can be achieved either by using conjugates of ROS amplifiers with ligands binding to receptors expressed on neutrophils (e.g., the GPI-anchored myeloid differentiation marker Ly6G or FPR) or by designing reagents activated by neutrophil function [e.g., phagocytic activity or enzymatic activity of neutrophil elastase (NE)]. Since binding of an artificial ligand to a receptor may trigger or inhibit priming of neutrophils the latter approach has a smaller potential for severe side effects and is probably better suitable for therapy. Here, we review current approaches for the use of ROS amplifiers and discuss their applicability for treatment. As an example, we suggest a possible design of neutrophil-specific ROS amplifiers, which are based on NE-activated ABPs.
EVALuna2:213257

Clearance Deficiency and Cell Death Pathways: A Model for the Pathogenesis of SLE - Mahajan, Aparna; Herrmann, Martin; Munoz, Luis Enrique (Frontiers in Immunology, 2016)
Alterations of cell death pathways, including apoptosis and the neutrophil specific kind of death called NETosis, can represent a potential source of autoantigens. Defects in the clearance of apoptotic cells may be responsible for the initiation of systemic autoimmunity in several chronic inflammatory diseases, including systemic lupus erythematosus (SLE). Autoantigens are released mainly from secondary necrotic cells because of a defective clearance of apoptotic cells or an inefficient degradation of DNA-containing neutrophil extracellular traps (NETs). These modified autoantigens are presented by follicular dendritic cells to autoreactive B cells in germinal centers of secondary lymphoid organs. This results in the loss of self-tolerance and production of autoantibodies, a unifying feature of SLE. Immune complexes (IC) are formed from autoantibodies bound to uncleared cellular debris in blood or tissues. Clearance of IC by blood phagocytes, macrophages, and dendritic cells leads to proinflammatory cytokine secretion. In particular, plasmacytoid dendritic cells produce high amounts of interferon-? upon IC uptake, thereby contributing to the interferon signature of patients with SLE. The clearance of antinuclear IC via Fc-gamma receptors is considered a central event in amplifying inflammatory immune responses in SLE. Along with this, the accumulation of cell remnants represents an initiating event of the etiology, while the subsequent generation of autoantibodies against nuclear antigens (including NETs) results in the perpetuation of inflammation and tissue damage in patients with SLE. Here, we discuss the implications of defective clearance of apoptotic cells and NETs in the development of clinical manifestations in SLE.
EVALuna2:13259

Cleaved N-terminal histone tails distinguish between NADPH oxidase (NOX)-dependent and NOX-independent pathways of neutrophil extracellular trap formation - Pieterse, Elmar; Rother, Nils; Yanginlar, Cansu; Gerretsen, Jelle; Boeltz, Sebastian; Munoz, Luis Enrique; Herrmann, Martin; Pickkers, Peter; Hilbrands, Luuk B.; Van Der Vlag, Johan (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: Neutrophil extracellular traps (NETs) act in various rheumatic diseases. Although NET formation was originally described as a nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-dependent pathway, it appears that there are also NOX-independent pathways of NET release. Currently, no tools are available that can discriminate between both NET-forming pathways. We aimed to develop a serological method allowing the discrimination between NETs generated through NOX-dependent or NOX-independent pathways. METHODS: Histones from in vitro generated NOX-dependent and NOX-independent NETs were characterised with a panel of lupus-derived antibodies against N-terminal histone tails using immunofluorescence microscopy, western blot and ELISA. NETs in patients with NET-associated diseases, that is, rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriatic arthritis (PsA) and sepsis, were characterised in sandwich ELISAs employing antibodies against myeloperoxidase (MPO) and N-terminal histone tails as detecting and capturing antibodies, respectively. Functional responses of endothelial cells to NOX-dependent and NOX-independent NETs were assessed as well. RESULTS: Neutrophil elastase cleaves the N-terminal tails of core histones during NOX-dependent, but not during NOX-independent NET formation. Consequently, the detection of MPO-histone complexes with antibodies against N-terminal histone tails allows discrimination between NETs formed through a NOX-dependent or NOX-independent manner. Characterisation of in vivo circulating NETs revealed the presence of NOX-independent NETs in RA, SLE and sepsis, but NOX-dependent NETs in PsA. NOX-independent NETs displayed an increased capacity to activate endothelial cells when compared with NOX-dependent NETs. CONCLUSIONS: These results indicate heterogeneity in NET-forming pathways in vivo and highlight the need for disease-specific strategies to prevent NET-mediated pathology.
EVALuna2:34475

Cleaved N-terminal histone tails distinguish between NADPH oxidase (NOX)-dependent and NOX-independent pathways of neutrophil extracellular trap formation - Pieterse, Elmar; Rother, Nils; Yanginlar, Cansu; Gerretsen, Jelle; Böltz, Sebastian; Munoz, Luis Enrique; Herrmann, Martin; Pickkers, Peter; Hilbrands, Luuk B.; Van Der Vlag, Johan (Annals of the Rheumatic Diseases, 2018)
Keywords: inflammation; psoriatic arthritis; autoimmune diseases; rheumatoid arthritis; systemic lupus erythematosus

Connection between periodontitis-induced low-grade endotoxemia and systemic diseases: Neutrophils as protagonists and targets - Vitkov, Ljubomir; Munoz Becerra, Luis; Knopf, Jasmin; Oberthaler, Hannah; Minnich, Bernd; Hannig, Matthias; Herrmann, Martin; Schauer, Christine (International Journal of Molecular Sciences, 2021)
Periodontitis is considered a promoter of many systemic diseases, but the signaling pathways of this interconnection remain elusive. Recently, it became evident that certain microbial challenges promote a heightened response of myeloid cell populations to subsequent infections either with the same or other pathogens. This phenomenon involves changes in the cell epigenetic and transcription, and is referred to as “trained immunity”. It acts via modulation of hematopoietic stem and progenitor cells (HSPCs). A main modulation driver is the sustained, persistent low-level transmission of lipopolysaccharide from the periodontal pocket into the peripheral blood. Subsequently, the neutrophil phenotype changes and neutrophils become hyper-responsive and prone to boosted formation of neutrophil extracellular traps (NET). Cytotoxic neutrophil proteases and histones are responsible for ulcer formations on the pocket epithelium, which foster bacteremia and endoxemia. The latter promote systemic low-grade inflammation (SLGI), a precondition for many systemic diseases and some of them, e.g., atherosclerosis, diabetes etc., can be triggered by SLGI alone. Either reverting the polarized neutrophils back to the homeostatic state or attenuation of neutrophil hyper-responsiveness in periodontitis might be an approach to diminish or even to prevent systemic diseases.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Blood transmission of PAMPs; Loss of tolerance; Neutrophil hyper-responsiveness; Neutrophil-driven damages; Trained immunity

Corrigendum: Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial(Front. Immunol., (2021), 12, (740742), 10.3389/fimmu.2021.740742) - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2022)
In the original article, there was an error. The mistake is found in the sentence “While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells.” in the abstract of the article.
CRIS-Team Scopus Importer:2022-03-04
Keywords: chronic degenerative and inflammatory diseases; immune status; immunophenotyping; low dose radiation therapy (LDRT); subjective pain level; x-rays

Cytotoxicity of crystals involves RIPK3-MLKL-mediated necroptosis - Mulay, Shrikant R.; Desai, Jyaysi; Kumar, Santhosh V.; Eberhard, Jonathan N.; Thomasova, Dana; Romoli, Simone; Grigorescu, Melissa; Kulkarni, Onkar P.; Popper, Bastian; Vielhauer, Volker; Zuchtriegel, Gabriele; Reichel, Christoph; et al. (Nature Communications, 2016)
Crystals cause injury in numerous disorders, and induce inflammation via the NLRP3 inflammasome, however, it remains unclear how crystals induce cell death. Here we report that crystals of calcium oxalate, monosodium urate, calcium pyrophosphate dihydrate and cystine trigger caspase-independent cell death in five different cell types, which is blocked by necrostatin-1. RNA interference for receptor-interacting protein kinase 3 (RIPK3) or mixed lineage kinase domain like (MLKL), two core proteins of the necroptosis pathway, blocks crystal cytotoxicity. Consistent with this, deficiency of RIPK3 or MLKL prevents oxalate crystal-induced acute kidney injury. The related tissue inflammation drives TNF-?-related necroptosis. Also in human oxalate crystal-related acute kidney injury, dying tubular cells stain positive for phosphorylated MLKL. Furthermore, necrostatin-1 and necrosulfonamide, an inhibitor for human MLKL suppress crystal-induced cell death in human renal progenitor cells. Together, TNF-?/TNFR1, RIPK1, RIPK3 and MLKL are molecular targets to limit crystal-induced cytotoxicity, tissue injury and organ failure.
EVALuna2:13240

Dying autologous cells as instructors of the immune system - Munoz Becerra, Luis; Herrmann, Martin; Berens, Christian (Clinical and Experimental Immunology, 2015)
In an organism, cell death occurs at many different sites and in many different forms. It is frequently part of normal development or serves to maintain cell homeostasis. In other cases, cell death not only occurs due to injury, disease or infection, but also as a consequence of various therapeutic interventions. However, in all of these scenarios, the immune system has to react to the dying and dead cells and decide whether to mount an immune response, to remain quiet or to initiate healing and repopulation. This is essential for the organism, testified by many diseases that are associated with malfunctioning in the cell death process, the corpse removal, or the ensuing immune responsiveness. Therefore, dying cells generally have to be considered as instructors of the immune system. How this happens and which signals and pathways contribute to modulate or shape the immune response is still elusive in many conditions. The articles presented in this Special Issue address such open questions. They highlight that the context in which cell death occurs will not only influence the cell death process itself, but also affect the surrounding cellular milieu, how the generation and presence of 'eat me' signals can have an impact on cell clearance, and that the exact nature of the residual 'debris' and how it is processed are fundamental to determining the immunological consequences. Hopefully, these articles initiate new approaches and new experiments to complete our understanding of how cell death and the immune system interact with each other.
EVALuna2:13095

Early Histopathological Changes of the Salivary Glands Associated with the Development of Primary Sjogren's Syndrome - Shan, Xiaomei; Reichardt, Clara; Singh, Jeeshan; Zeitler, Anne; Schauer, Christine; Knopf, Jasmin; Herrmann, Martin; Grossmayer, Gerhard; Schett, Georg; Munoz, Luis Enrique (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Editorial: NETosis 2: The Excitement Continues - Munoz, Luis Enrique; Kaplan, Mariana J.; Radic, Marko; Herrmann, Martin; Munoz Becerra, Luis (Frontiers in Immunology, 2017)
EVALuna2:13519

Elevated Serum Lysophosphatidylcholine in Patients with Systemic Lupus Erythematosus Impairs Phagocytosis of Necrotic Cells In Vitro - Grossmayer, Gerhard E.; Keppeler, Hildegard; Boeltz, Sebastian; Janko, Christina; Rech, Jürgen; Herrmann, Martin; Lauber, Kirsten; Munoz, Luis Enrique; Munoz Becerra, Luis (Frontiers in Immunology, 2017)
Impaired clearance of dying and dead cells by professional and amateur phagocytes plays a crucial role in the etiology of systemic lupus erythematosus (SLE). While dying, cells expose and release a plethora of eat-me and find-me signals to ensure their timely removal before entering the dangerous stage of secondary necrosis. A well-described chemoattractant for macrophages is dying cell-derived lysophosphatidylcholine (LPC). However, its implications for and/or its association with SLE disease, so far, have not been examined. In the present study, we analyzed the LPC serum concentrations of patients with SLE and rheumatoid arthritis (RA). Subsequently, we examined if and to which extent the measured serum concentrations of LPC and an LPC-rich environment can impact the phagocytosis of necrotic cells.Sera from patients with SLE, RA, and normal healthy donors (NHD) were characterized for several parameters, including LPC concentrations. Phagocytosis of dead cells by human macrophages in the presence of SLE and NHD sera was quantified. Additionally, the impact of exogenously added, purified LPC on phagocytosis was analyzed.Patients with SLE had significantly increased LPC serum levels, and high serum LPC of SLE patients correlated significantly with impaired phagocytosis of dead cells in the presence of heat-inactivated serum. Phagocytosis in the presence of sera from NHD showed no correlation to LPC levels, but exogenous addition of purified LPC in the range as measured in SLE patients' sera led to a concentration-dependent decrease.Our data show that high levels of LPC as observed in the sera of SLE patients have a negative impact on the clearance of dead cells by macrophages. Chemoattraction requires a concentration gradient. The higher the LPC concentration surrounding a dying or dead cell, the smaller the achievable gradient upon LPC release will be. Thus, it is feasible to assume that elevated LPC levels can interfere with the build-up of a local LPC gradient during cell death, and hence might play a role in the establishment and/or perpetuation of SLE disease.
EVALuna2:13530

Elevated serum lysophosphatidylcholine in patients with systemic lupus erythematosus impairs phagocytosis of necrotic cells in vitro - Grossmayer, Gerhard E.; Keppeler, Hildegard; Böltz, Sebastian; Janko, Christina; Rech, Jürgen; Herrmann, Martin; Lauber, Kirsten; Munoz, Luis Enrique (Frontiers in Immunology, 2018)
Keywords: Lysophosphatidylcholine; Necrotic cells; Clearance deficiency; Efferocytosis; Serum; Systemic lupus erythematosus; Phagocytosis; Rheumatoid arthritis

Experimental lupus is aggravated in mouse strains with impaired induction of neutrophil extracellular traps - Kienhofer, Deborah; Hahn, Jonas; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Urbonaviciute, Vilma; Johnsson, Caroline; Maueröder, Christian; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; Harrer, Thomas; et al. (JCI Insight, 2017)
Many effector mechanisms of neutrophils have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Neutrophil extracellular traps (NETs) have been assigned a particularly detrimental role. Here we investigated the functional impact of neutrophils and NETs on a mouse model of lupus triggered by intraperitoneal injection of the cell death-inducing alkane pristane. Pristane-induced lupus (PIL) was aggravated in 2 mouse strains with impaired induction of NET formation, i.e., NOX2-deficient (Ncf1-mutated) and peptidyl arginine deiminase 4-deficient (PAD4-deficient) mice, as seen from elevated levels of antinuclear autoantibodies (ANAs) and exacerbated glomerulonephritis. We observed a dramatically reduced ability to form pristane-induced NETs in vivo in both Ncf1-mutated and PAD4-deficient mice, accompanied by higher levels of inflammatory mediators in the peritoneum. Similarly, neutropenic Mcl-1ΔMyelo mice exhibited higher levels of ANAs, which indicates a regulatory function in lupus of NETs and neutrophils. Blood neutrophils from Ncf1-mutated and human individuals with SLE exhibited exuberant spontaneous NET formation. Treatment with specific chemical NOX2 activators induced NET formation and ameliorated PIL. Our findings suggest that aberrant NET is one of the factors promoting experimental lupus-like autoimmunity by uncontrolled release of inflammatory mediators.
EVALuna2:1833

Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052

Extracellular DNA traps in inflammation, injury and healing - Daniel, Christoph; Leppkes, Moritz; Munoz, Luis Enrique; Muñoz, Luis E.; Schley, Gunnar; Schett, Georg; Herrmann, Martin (Nature Reviews Nephrology, 2019)
Following strong activation signals, several types of immune cells reportedly release chromatin and granular proteins into the extracellular space, forming DNA traps. This process is especially prominent in neutrophils but also occurs in other innate immune cells such as macrophages, eosinophils, basophils and mast cells. Initial reports demonstrated that extracellular traps belong to the bactericidal and anti-fungal armamentarium of leukocytes, but subsequent studies also linked trap formation to a variety of human diseases. These pathological roles of extracellular DNA traps are now the focus of intensive biomedical research. The type of pathology associated with the release of extracellular DNA traps is mainly determined by the site of trap formation and the way in which these traps are further processed. Targeting the formation of aberrant extracellular DNA traps or promoting their efficient clearance are attractive goals for future therapeutic interventions, but the manifold actions of extracellular DNA traps complicate these approaches.
CRIS-Team Scopus Importer:2019-07-09

Formation and Clearance of NETs in Health and Disease. - Knopf, Jasmin; Mahajan, Aparna; Munoz, Luis Enrique; Herrmann, Martin (Cells, 2022)
Neutrophils are the most abundant innate immune cells in humans and the first line of defense against invading pathogens [...].
EVALuna2:521519

Frontline Science: Aggregated neutrophil extracellular traps prevent inflammation on the neutrophil-rich ocular surface - Mahajan, Aparna; Grüneboom, Anika; Petru, Lenka; Podolska, Malgorzata; Kling, Lasse; Maueröder, Christian; Dahms, Florian; Christiansen, Silke; Günter, Lochnit; Krenn, Veit; Jünemann, Anselm; Bock, Felix; et al. (Journal of Leukocyte Biology, 2019)
Eye rheum is a physiological discharge, which accumulates at the medial angle of the healthy eye soon after opening in the morning. Microscopic evaluation of eye rheum revealed the presence of viable neutrophils, bacteria, epithelial cells, and particles, aggregated by neutrophil extracellular traps. We observed that in the evening, during eye closure, high C5a recruited neutrophils to the tear film and activated them. In this hypoxic area rich in CO 2 , neutrophils fight microbial aggressors by degranulation. Immediately after eye opening, the microenvironment of the ocular surface changes, the milieu gets normoxic, and loss of CO 2 induces subtle alkalinization of tear film. These conditions favored the formation of neutrophil extracellular traps (NETs) that initially covers the ocular surface and tend to aggregate by eyelid blinking. These aggregated neutrophil extracellular traps (aggNETs) are known as eye rheum and contain several viable neutrophils, epithelial cells, dust particles, and crystals packed together by NETs. Similar to aggNETs induced by monosodium urate crystals, the eye rheum shows a robust proteolytic activity that degraded inflammatory mediators before clinically overt inflammation occur. Finally, the eye rheum passively floats with the tear flow to the medial angle of the eye for disposal. We conclude that the aggNETs-based eye rheum promotes cleaning of the ocular surface and ameliorates the inflammation on the neutrophil-rich ocular surfaces.
CRIS-Team Scopus Importer:2019-05-02
Keywords: degranulation; eye rheum; inflammation; NETs; neutrophils; resolution; serine protease

Glutathione peroxidase 3 is a novel clinical diagnostic biomarker and potential therapeutic target for neutrophils in rheumatoid arthritis - Chen, Tao; Zhou, Zhen; Peng, Minge; Hu, Huifang; Sun, Rui; Xu, Jiayi; Zhu, Chenxi; Li, Yanhong; Zhang, Qiuping; Luo, Yubin; Yang, Bin; Dai, Lunzhi; et al. (Arthritis Research & Therapy, 2023)
Background: Neutrophils have a critical role in the pathogenesis of rheumatoid arthritis (RA) with immune system dysfunction. However, the molecular mechanisms of this process mediated by neutrophils still remain elusive. The purpose of the present study is to identify hub genes in neutrophils for diagnosis and treatment of RA utilizing publicly available datasets. Methods: Gene expression profiles were downloaded from the Gene Expression Omnibus, and batch-corrected and normalized expression data were obtained using the ComBat package. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis were used to conduct significantly functional analysis and crucial pathways. The resulting co-expression genes modules and hub genes were generated based on the weighted gene co-expression network analysis and visualization by Cytoscape. Flow cytometry was conducted to detect reactive oxygen species (ROS) levels in neutrophils. Results: Neutrophils underwent transcriptional changes in synovial fluid (SF) of RA patients, different from peripheral blood of healthy controls or patients with RA. Especially, glycolysis, HIF-1 signaling, NADH metabolism, and oxidative stress were affected. These hub genes were strongly linked with classical glycolysis-related genes (ENO1, GAPDH, and PKM) responsible for ROS production. The antioxidant enzyme glutathione peroxidase 3 (GPX3), a ROS scavenger, was first identified as a hub gene in RA neutrophils. Neutrophils from patients with autoinflammatory and autoimmune diseases had markedly enhanced ROS levels, most notably in RA SF. Conclusion: This research recognized hub genes and explored the characteristics of neutrophils in RA. Our findings suggest that the novel hub gene GPX3 is involved in the neutrophil-driven oxidative stress-mediated pathogenesis of RA. It has the potency to be a target for neutrophil-directed RA therapy.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Hub genes; Neutrophils; Reactive oxygen species; Rheumatoid arthritis

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Graphene Oxide Nanosheets for Localized Hyperthermia-Physicochemical Characterization, Biocompatibility, and Induction of Tumor Cell Death - Podolska, Malgorzata; Barras, Alexandre; Alexiou, Christoph; Frey, Benjamin; Gaipl, Udo; Boukherroub, Rabah; Szunerits, Sabine; Janko, Christina; Munoz, Luis Enrique (Cells, 2020)
Background: The main goals of cancer treatment are not only to eradicate the tumor itself but also to elicit a specific immune response that overcomes the resistance of tumor cells against chemo- and radiotherapies. Hyperthermia was demonstrated to chemo- and radio-sensitize cancerous cells. Many reports have confirmed the immunostimulatory effect of such multi-modal routines. Methods: We evaluated the interaction of graphene oxide (GO) nanosheets; its derivatives reduced GO and PEGylated rGO, with components of peripheral blood and evaluated its thermal conductivity to induce cell death by localized hyperthermia. Results: We confirmed the sterility and biocompatibility of the graphene nanomaterials and demonstrated that hyperthermia applied alone or in the combination with radiotherapy induced much more cell death in tumor cells than irradiation alone. Cell death was confirmed by the release of lactate dehydrogenase from dead and dying tumor cells. Conclusion: Biocompatible GO and its derivatives can be successfully used in graphene-induced hyperthermia to elicit tumor cell death.
CRIS-Team WoS Importer:2020-05-15

Guidelines for the use of flow cytometry and cell sorting in immunological studies - Cossarizza, Andrea; Chang, Hyun-Dong; Radbruch, Andreas; Akdis, Mubeccel; Andrae, Immanuel; Annunziato, Francesco; Bacher, Petra; Barnaba, Vincenzo; Battistini, Luca; Bauer, Wolfgang M.; Baumgart, Sabine; Becher, Burkhard; et al. (European Journal of Immunology, 2017)
EVALuna2:13453

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Hidden Appendicoliths and Their Impact on the Severity and Treatment of Acute Appendicitis - Dölling, Maximilian; Rahimli, Mirhasan; Pachmann, Jonas; Szep, Malik; Al-Madhi, Sara; Andric, Mihailo; Kahlert, Ulf D.; Hofmann, Tobias; Boettcher, Michael; Munoz, Luis Enrique; Herrmann, Martin; Perrakis, Aristotelis; et al. (Journal of Clinical Medicine, 2024)
Background/Objectives: In patients diagnosed with uncomplicated acute appendicitis (UAA), the absence of calcified deposits or stones, called appendicoliths, often leads to consideration of non-operative treatment (NOT), despite the notable treatment failure rate associated with this approach. Previous research has indirectly estimated the prevalence of appendicoliths to range between 15% and 38% retrospectively by CT scan, intraoperative palpation, and pathology report, thereby potentially missing certain concrements. Our hypothesis proposes that this reported prevalence significantly underestimates the occurrence of appendicoliths, which could explain the high failure rate of 29% of patients with appendicitis observed with NOT. Methods: In our prospective study, conducted with a cohort of 56 adult patients diagnosed with acute appendicitis (AA), we employed intraoperative extracorporeal incisions of the vermiform appendix, in addition to standard diagnostic methods. Results: Our findings revealed 50% more appendicoliths by intraoperative incision (n = 36, p < 0.001) compared to preoperative imaging (n = 24). Appendicoliths were present in 71.4% (n = 40, p < 0.001) of AA patients. Conclusions: These results suggest that conventional diagnostic procedures plausibly underestimate the actual prevalence of appendicoliths, potentially elucidating the frequent treatment failures observed in NOT approaches applied to patients with UAA.
CRIS-Team Scopus Importer:2024-08-23
Keywords: acute appendicitis; appendicoliths; faecoliths; perforated appendicitis

Hypoxia Promotes Neutrophil Survival After Acute Myocardial Infarction - Dölling, Maximilian; Eckstein, Markus; Singh, Jeeshan; Schoen, Janina; Shan, Xiaomei; Bozec, Aline; Knopf, Jasmin; Schett, Georg; Munoz Becerra, Luis; Herrmann, Martin; Schauer, Christine (Frontiers in Immunology, 2022)
Phagocytosis, degranulation, and neutrophil extracellular traps (NETs) formation build the armory of neutrophils for the first line of defense against invading pathogens. All these processes are modulated by the microenvironment including tonicity, pH and oxygen levels. Here we investigated the neutrophil infiltration in cardiac tissue autopsy samples of patients with acute myocardial infarction (AMI) and compared these with tissues from patients with sepsis, endocarditis, dermal inflammation, abscesses and diseases with prominent neutrophil infiltration. We observed many neutrophils infiltrating the heart muscle after myocardial infarction. Most of these had viable morphology and only few showed signs of nuclear de-condensation, a hallmark of early NET formation. The abundance of NETs was the lowest in acute myocardial infarction when compared to other examined diseases. Since cardiac oxygen supply is abruptly abrogated in acute myocardial infarction, we hypothesized that the resulting tissue hypoxia increased the longevity of the neutrophils. Indeed, the viable cells showed increased nuclear hypoxia inducible factor-1α (HIF-1α) content, and only neutrophils with low HIF-1α started the process of NET formation (chromatin de-condensation and nuclear swelling). Prolonged neutrophil survival, increased oxidative burst and reduced NETs formation were reproduced under low oxygen tensions and by HIF-1α stabilization in vitro. We conclude that nuclear HIF-1α is associated with prolonged neutrophil survival and enhanced oxidative stress in hypoxic areas of AMI.
CRIS-Team Scopus Importer:2022-03-04
Keywords: acute myocardial infarction; DNA decondensation; hypoxia inducible factor 1; NET formation; neutrophil extracellular traps; neutrophils

IgA2 Antibodies against SARS-CoV-2 Correlate with NET Formation and Fatal Outcome in Severely Diseased COVID-19 Patients - Staats, Leonie A. N.; Pfeiffer, Hella; Knopf, Jasmin; Lindemann, Aylin; Fürst, Julia; Kremer, Andreas; Hackstein, Holger; Neurath, Markus; Munoz, Luis Enrique; Achenbach, Susanne; Leppkes, Moritz; Herrmann, Martin; et al. (Cells, 2020)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leads to an adaptive immune response in the host and the formation of anti-SARS-CoV-2 specific antibodies. While IgG responses against SARS-CoV-2 have been characterized quite well, less is known about IgA. IgA2 activates immune cells and induces inflammation and neutrophil extracellular trap (NET) formation which may contribute to organ injury and fatal outcome in SARS-CoV-2-infected patients. SARS-CoV-2 spike protein specific antibody levels were measured in plasma samples of 15 noninfected controls and 82 SARS-CoV-2-infected patients with no or mild symptoms, moderate symptoms (hospitalization) or severe disease (intensive care unit, ICU). Antibody levels were compared to levels of C-reactive protein (CRP) and circulating extracellular DNA (ecDNA) as markers for general inflammation and NET formation, respectively. While levels of SARS-CoV-2-specific IgG were similar in all patient groups, IgA2 antibodies were restricted to severe disease and showed the strongest discrimination between nonfatal and fatal outcome in patients with severe SARS-CoV-2 infection. While anti-SARS-CoV-2 IgG and IgA2 levels correlated with CRP levels in severely diseased patients, only anti-SARS-CoV-2 IgA2 correlated with ecDNA. These data suggest that the formation of anti-SARS-CoV-2 IgA2 during SARS-CoV-2 infection is a marker for more severe disease related to NET formation and poor outcome.
CRIS-Team WoS Importer:2021-01-15

IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

Improved diagnosis of systemic lupus erythematosus with human-derived double-stranded DNA antigen - Li, Xianming; Tang, Honghu; Chen, Chunyan; Niu, Qian; Zhou, Zhen; Zheng, Yantong; Liu, Yi; Munoz, Luis Enrique; Herrmann, Martin; Wu, Peng; Zhao, Yi (Biosensors and Bioelectronics, 2025)
Anti-double-stranded DNA antibodies (anti-dsDNA) serve as a crucial serological indicator for systemic lupus erythematosus (SLE). Chemiluminescent immunoassay (CIA) is mainly used in clinical diagnosis of SLE, but suffers from low specificity, partially because the use of dsDNA antigens of varied sources in current CIA kits that sometimes led to controversial results. On the basis that anti-dsDNA in healthy individuals tend to selectively bind with dsDNA originating from pathogens, whereas pathogenic anti-dsDNA in SLE patients bind all forms of dsDNA, here we proposed the use of dsDNA fragment derived from human genome as antigen (synthesized via PCR using the human genomic DNA as the template). A magnetic bead-based immunofluorescence assay (IFA) was thus developed for SLE diagnosis, which exhibited improved sensitivity and specificity over CIA using the WHO reference reagent (15/174) as standard. For clinical serum sample analysis (n = 590), IFA exhibited an accuracy of 71.9% that was higher than CIA (65.3%). Crucially, the IFA results exhibited stronger correlations with the activity of SLE, renal involvement, and its prognosis. Besides the improved clinical diagnosis, the proposed IFA also holds great promise in assay standardization due to the high homogeneity of the synthetic dsDNA.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Anti-dsDNA antibody; Immunofluorescence assay; Standardization; Systemic lupus erythematosus

Induction of Ocular Surface Inflammation and Collection of Involved Tissues - Singh, Jeeshan; Shan, Xiaomei; Mahajan, Aparna; Herrmann, Martin; Schauer, Christine; Knopf, Jasmin; Munoz Becerra, Luis (Journal of Visualized Experiments, 2022)
Ocular surface diseases include a range of disorders that disturb the functions and structures of the cornea, conjunctiva, and the associated ocular surface gland network. Meibomian glands (MG) secrete lipids that create a covering layer that prevents the evaporation of the aqueous part of the tear film. Neutrophils and extracellular DNA traps populate MG and the ocular surface in a mouse model of allergic eye disease. Aggregated neutrophil extracellular traps (aggNETs) formulate a mesh-like matrix composed of extracellular chromatin that occludes MG outlets and conditions MG dysfunction. Here, a method for inducing ocular surface inflammation and MG dysfunction is presented. The procedures for collecting organs related to the ocular surface, such as the cornea, conjunctiva, and eyelids, are described in detail. Using established techniques for processing each organ, the major morphological and histopathological features of MG dysfunction are also shown. Ocular exudates offer the opportunity to assess the inflammatory state of the ocular surface. These procedures enable the investigation of topical and systemic anti-inflammatory interventions at the preclinical level.
CRIS-Team Scopus Importer:2022-09-02

Inhibitory and Agonistic Autoantibodies Directed Against the β2-Adrenergic Receptor in Pseudoexfoliation Syndrome and Glaucoma - Hohberger, Bettina; Schlötzer-Schrehardt, Ursula; Mardin, Christian; Lämmer, Robert; Munoz, Luis Enrique; Kunze, Rudolf; Herrmann, Martin; Wallukat, Gerd (Frontiers in Neuroscience, 2021)
Pseudoexfoliation syndrome (PEXS) and glaucoma (PEXG) are assumed to be caused by a generalized elastosis leading to the accumulation of PEX material in ocular as well as in extraocular tissues. The exact pathophysiology of PEXS is still elusive. PEXG, the most common type of secondary open-angle glaucoma (OAG), is characterized by large peaks of intraocular pressure (IOP) with a progressive loss of the visual field. Agonistic autoantibodies (agAAbs) against the β2-adrenergic receptor (AR) have been shown to be present in sera of patients with primary and secondary OAG and ocular hypertension and are seemingly linked to IOP. In the present study, we investigated the autoantibodies directed against the β2-AR in sera of patients with PEXS and PEXG. We recruited 15, 10, and 15 patients with PEXG, PEXS, and primary OAG, respectively. Ten healthy individuals served as controls. All patients underwent standard ophthalmological examination with Octopus G1 perimetry. agAAbs prepared from serum samples were analyzed in a rat cardiomyocyte–based bioassay for the presence of agAAbs. We identified the interacting loop of the β2-AR and the immunoglobulin G (IgG) subclasses using synthetic peptides corresponding to the extracellular loops of the receptors and enzyme-linked immunosorbent assay, respectively. None of the controls were β2-agAAb–positive (0.2 ± 0.5 U). No β2-agAAbs (0.2 ± 0.4 U), but inhibitory β2-AAbs were observed in 80% of the patients that partially blocked the drug-induced β2-adrenergic stimulation; 5.8 ± 1.7 U vs. 11.1 ± 0.9 U for clenbuterol in the absence and the presence of sera from patients with PEXS, respectively. Epitope analyses identified the third extracellular loop of the β2-AR as the target of the inhibitory β2-AAbs, being of IgG3 subtype in PEXS patients. In contrast, patients with PEXG showed β2-agAAbs (5.6 ± 0.9 U), but no inhibitory ones. The β2-agAAbs levels of patients with PEXG and primary OAG patients (3.9 ± 2.8 U; p > 0.05) were at a similar level. In two cases of PEXG, the β2-agAAbs exert synergistic effects with clenbuterol. The activity increased from 11.5 ± 0.3 (clenbuterol only) to 16.3 ± 0.9 U. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma, agonistic and inhibitory β2-AAbs seem to be a part of this multifactorial interplay.
CRIS-Team Scopus Importer:2021-09-03
Keywords: autoantibodies; glaucoma; imbalanced autonomic theory; pseudoexfoliation; β

Inosine Released from Dying or Dead Cells Stimulates Cell Proliferation via Adenosine Receptors - Chen, Jin; Chaurio, Ricardo A.; Maueröder, Christian; Derer, Anja; Rauh, Manfred; Kost, Andriy; Liu, Yi; Mo, Xianming; Hueber, Axel; Bilyy, Rostyslav; Herrmann, Martin; Zhao, Yi; et al. (Frontiers in Immunology, 2017)
Many antitumor therapies induce apoptotic cell death in order to cause tumor regression. Paradoxically, apoptotic cells are also known to promote wound healing, cell proliferation, and tumor cell repopulation in multicellular organisms. We aimed to characterize the nature of the regenerative signals concentrated in the micromilieu of dead and dying cells.Cultures of viable melanoma B16F10 cells, mouse fibroblasts, and primary human fibroblast-like synoviocytes (FLS) in the presence of dead and dying cells, their supernatants (SNs), or purified agonists and antagonists were used to evaluate the stimulation of proliferation. Viable cell quantification was performed by either flow cytometry of harvested cells or by crystal violet staining of adherent cells. High-performance liquid chromatography and liquid chromatography coupled with mass spectrometry of cell SNs were deployed to identify the nature of growth-promoting factors. Coimplantation of living cells in the presence of SNs collected from dead and dying cells and specific agonists was used to evaluate tumor growth in vivo.The stimulation of proliferation of few surviving cells by bystander dead cells was confirmed for melanoma cells, mouse fibroblasts, and primary FLS. We found that small soluble molecules present in the protein-free fraction of SNs of dead and dying cells were responsible for the promotion of proliferation. The nucleoside inosine released by dead and dying cells acting via adenosine receptors was identified as putative inducer of proliferation of surviving tumor cells after irradiation and heat treatment.Inosine released by dead and dying cells mediates tumor cell proliferation via purinergic receptors. Therapeutic strategies surmounting this pathway may help to reduce the rate of recurrence after radio- and chemotherapy.
EVALuna2:13419

Integrin αVβ6: Autoantigen and Driver of Epithelial Remodeling in Colon and Bile Ducts in Primary Sclerosing Cholangitis and Inflammatory Bowel Disease. - Roth, Dominik; Düll, Miriam; Horst, Ludwig J.; Lindemann, Aylin; Malzer, Xenia; Koop, Kristina; Zundler, Sebastian; Vetter, Marcel; Jefremow, André; Atreya, Raja; Geppert, Carol-Immanuel; Weidemann, Sören; et al. (Journal of Crohns & Colitis, 2025)
BACKGROUND: Recently, autoantibodies directed against the epithelial adhesion protein integrin αVβ6 have been identified that are strongly associated with ulcerative colitis (UC). We aimed to elucidate whether anti-integrin αVβ6 (anti-αVβ6) is present in primary sclerosing cholangitis (PSC), its associated inflammatory bowel disease, or other cholestatic liver diseases and their persistence after proctocolectomy. METHODS: We detected anti-αVβ6 by an enzyme-linked immunosorbent assay in sera collected at 2 German tertiary centers, including healthy controls (N = 62), UC (N = 36), Crohn's disease (CD, N = 65), PSC-inflammatory bowel diseases (IBD) (78 samples from N = 41 patients), PSC without IBD (PSC, 41 samples from N = 18 patients), primary biliary cholangitis (PBC, N = 24), autoimmune hepatitis (AIH, N = 32), secondary sclerosing cholangitis (SSC, N = 12), and metabolic dysfunction-associated steatotic liver disease (MASLD, N = 24). In addition, sera after proctocolectomy were studied (44 samples/N = 10 patients). Immunofluorescent analyses were performed in tissue samples from liver, large bile duct from surgical resections, and colon of PSC patients. RESULTS: Anti-αVβ6 occurred in 91% of UC, 17% of CD, 73% of PSC-IBD, 39% of PSC, 4% of PBC, 14% of AIH, and 0% of healthy controls, SSC, or MASLD. Integrin αVβ6 is selectively expressed in disease-associated epithelia of both bile duct and colon. Anti-αVβ6 levels correlate moderately with intestinal disease activity in PSC-IBD, but only weakly with biliary disease. CONCLUSIONS: Anti-αVβ6 frequently occurs in patients suffering from PSC, especially in PSC-IBD. Anti-αVβ6 levels positively correlate to IBD activity in PSC-IBD, but may also occur in the absence of clinically manifest IBD in PSC.
EVALuna2:578869

Loading of nuclear autoantigens prototypically recognized by systemic lupus erythematosus sera into late apoptotic vesicles requires intact microtubules and myosin light chain kinase activity - Zirngibl, Matthias; Fuernrohr, B. G.; Janko, Christina; Munoz, L. E.; Voll, R. E.; Gregory, C. D.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Clinical and Experimental Immunology, 2015)
Most cases of systemic lupus erythematosus (SLE) are characterized by an impaired clearance of apoptotic cells in various tissues. Non-cleared apoptotic waste is considered an immunogen driving the autoimmune response in patients with SLE. During the execution of apoptosis, membrane blebs are formed and filled with cellular components. Here, we evaluate the cytoskeletal pathway(s) responsible for the loading of SLE prototypic nuclear autoantigens into the apoptotic cell-derived membranous vesicles (ACMV) generated during late phases of apoptosis. HeLa cells expressing a fusion protein of histone H2B with green fluorescent protein (GFP) were irradiated with ultraviolet (UV)-B to induce apoptosis. The appearance and trafficking of chromatin-derived material was monitored by fluorescence microscopy. Specific inhibitors of cytoskeletal pathways were employed to identify the motile elements involved in translocation and trafficking of the nuclear components. We observed that immediately after their appearance the ACMV did not contain histone H2B(GFP) ; in this phase the fluorescence was contained in the nuclear remnants and the cytoplasm. Within consecutive minutes the ACMV were loaded with chromatin-derived material, whereas the loading of simultaneously created ACMV with histone H2B(GFP) was not uniform. Some ACMV were preferentially filled and, consequently, showed a remarkably higher histone H2B(GFP) accumulation. Inhibitors of the cytoskeleton revealed that functional microtubules and myosin light chain kinase are required for nuclear shrinkage and loading of nuclear material into the ACMV, respectively.
EVALuna2:12985

Low amounts of bisecting glycans characterize cerebrospinal fluid-borne IgG - Knopf, Jasmin; Magorivska, Iryna; Maier, Jan-Niklas; Spitzer, Philipp; Bilyy, Rostyslav; Biermann, Mona; Hychka, Kateryna; Bondt, Albert; Wuhrer, Manfred; Toes, Rene E. M.; Schett, Georg; Herrmann, Martin; et al. (Journal of Neuroimmunology, 2018)
Immunoglobulin G (IgG) harbors a conserved N-glycosylation site which is important for its effector functions. Changes in glycosylation of IgG occur in many autoimmune diseases but also in physiological conditions. Therefore, the glycosylation pattern of serum IgG is well characterized. However, limited data is available on the glycosylation pattern of IgG in cerebrospinal fluid (CSF) compared to serum. Here, we report significantly reduced levels of bisected glycans in CSF IgG. Galactosylation and sialylation of IgG4 also differed significantly. Therefore, we propose a common mechanism mediating glycosylation changes of IgG at the transition from serum to CSF in steady state conditions.
EVALuna2:34466

Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2021)
The treatment of chronic inflammatory and degenerative diseases by low dose radiation therapy (LDRT) is promising especially for patients who were refractory for classical therapies. LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has been applied since the late 19th century, the immunological mechanisms remain elusive. Within the prospective IMMO-LDRT01 trial (NCT02653079) the effects of LDRT on the peripheral blood immune status, as well as on pain and life quality of patients have been analyzed. Blood is taken before and after every serial irradiation with a single dose per fraction of 0.5Gy, as well as during follow-up appointments in order to determine a detailed longitudinal immune status by multicolor flow cytometry. Here, we report the results of an interim analysis of 125 patients, representing half the number of patients to be recruited. LDRT significantly improved patients' pain levels and induced distinct systemic immune modulations. While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells. Furthermore, activated immune cells were decreased following LDRT. Especially cells of the monocytic lineage correlated to LDRT-induced improvements of clinical symptoms, qualifying these immune cells as predictive biomarkers for the therapeutic success. We conclude that LDRT improves pain of the patients by inducing systemic immune modulations and that immune biomarkers could be defined for prediction by improved patient stratification in the future.
CRIS-Team WoS Importer:2021-11-12

Magnetic drug targeting reduces the chemotherapeutic burden on circulating leukocytes - Janko, Christina; Dürr, Stephan; Munoz, Luis Enrique; Lyer, Stefan; Chaurio, Ricardo; Tietze, Rainer; Von Loehneysen, Sarah; Schorn, Christine; Herrmann, Martin; Alexiou, Christoph (International Journal of Molecular Sciences, 2013)
Magnetic drug targeting (MDT) improves the integrity of healthy tissues and cells during treatment with cytotoxic drugs. An anticancer drug is bound to superparamagnetic iron oxide nanoparticles (SPION), injected into the vascular supply of the tumor and directed into the tumor by means of an external magnetic field. In this study, we investigated the impact of SPION, mitoxantrone (MTO) and SPIONMTO on cell viability in vitro and the nonspecific uptake of MTO into circulating leukocytes in vivo. MDT was compared with conventional chemotherapy. MTO uptake and the impact on cell viability were assessed by flow cytometry in a Jurkat cell culture. In order to analyze MTO loading of circulating leukocytes in vivo, we treated tumor-bearing rabbits with MDT and conventional chemotherapy. In vitro experiments showed a dose-dependent MTO uptake and reduction in the viability and proliferation of Jurkat cells. MTO and SPIONMTO showed similar cytotoxic activity. Non-loaded SPION did not have any effect on cell viability in the concentrations tested. Compared with systemic administration in vivo, MDT employing SPIONMTO significantly decreased the chemotherapeutic load in circulating leukocytes. We demonstrated that MDT spares the immune system in comparison with conventional chemotherapy. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Immune system; Iron oxide nanoparticles; Leukocytes; Magnetic drug targeting; Mitoxantrone

Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Goesswein, Stefanie; Hahn, Jonas; Kienhoefer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz Becerra, Luis; Neurath, Markus; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study, we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (phorbol-2-myristate-13-acetate), ionomycin, monosodium urate, and LPS. In contrast, an acidic environment impaired NET formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to NET formation. Inflammatory foci may be characterized by an acidic environment. Our data indicate that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover, our findings highlight the necessity for strict pH control during assays of NET formation.
EVALuna2:2182

Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time

Microvesicles from cerebrospinal fluid of patients with Alzheimer’s disease display reduced concentrations of tau and APP protein - Spitzer, Philipp; Mulzer, Linda-Marie; Oberstein, Timo; Munoz, Luis Enrique; Lewczuk, Piotr; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel (Scientific Reports, 2019)
Microvesicles are small membranous particles generated during cellular activation or stress. The analysis of the content and the surface of microvesicles allow conclusions about the cells they are originating from and the underlying pathology. Therefore, CSF microvesicles have been suggested to be promising targets to monitor the (etio)pathology of neurodegenerative diseases. Microvesicles in the CSF of 15 patients with Alzheimer’s disease and 15 controls were analyzed by flow cytometry regarding the levels of CD3, CD4, CD45, CD64, BACE1, Aβ, APP and tau. The results were replicated in a second cohort comprising 14 patients with Alzheimer’s disease and 9 controls. The levels of tau and APP were reduced in microvesicles of Alzheimer’s disease patients. A significant change was neither observed in the number of microvesicles nor in the expression of the other antigens. Tau and APP in microvesicles separated patients with Alzheimer’s disease from controls with an AUC of 0.84 and 0.89 respectively. We conclude that tau and APP in CSF microvesicles are promising biomarkers which could directly provide information about the Alzheimer pathology on a cellular level.
CRIS-Team Scopus Importer:2019-05-21

Missing in action-The meaning of cell death in tissue damage and inflammation - Munoz Becerra, Luis; Leppkes, Moritz; Fuchs, Tobias A.; Hoffmann, Markus; Herrmann, Martin (Immunological Reviews, 2017)
Billions of cells die every day in higher organisms as part of the normal process of tissue homeostasis. During special conditions like in development, acute infections, mechanical injuries, and immunity, cell death is a common denominator and it exerts profound effects in the outcome of these scenarios. To prevent the accumulation of aged, superfluous, infected, damaged and dead cells, professional phagocytes act in a rapid and efficient manner to clear the battle field and avoid spread of the destruction. Neutrophils are the most abundant effector immune cells that extravasate into tissues and can turn injured tissues into gory battle fields. In peace times, neutrophils tend to patrol tissues without provoking inflammatory reactions. We discuss in this review actual and forgotten knowledge about the meaning of cell death during homeostatic processes and drive the attention to the importance of the action of neutrophils during patrolling and for the maintenance or recovery of the homeostatic state once the organism gets attacked or injured, respectively. In this fashion, we disclose several disease conditions that arise as collateral damage of physiological responses to death.
EVALuna2:13451

Neutrophil extracellular trap‐driven occlusive diseases - Yaykasli, Kürsat Oguz; Munoz, Luis Enrique; Mahajan, Aparna; Knopf, Jasmin; Schett, Georg; Herrmann, Martin; Schauer, Christine (Cells, 2021)
The enlightenment of the formation of neutrophil extracellular traps (NETs) as a part of the innate immune system shed new insights into the pathologies of various diseases. The initial idea that NETs are a pivotal defense structure was gradually amended due to several deleterious effects in consecutive investigations. NETs formation is now considered a double‐edged sword. The harmful effects are not limited to the induction of inflammation by NETs remnants but also include occlusions caused by aggregated NETs (aggNETs). The latter carries the risk of occluding tubular structures like vessels or ducts and appear to be associated with the pathologies of various diseases. In addition to life‐threatening vascular clogging, other occlusions include painful stone formation in the biliary system, the kidneys, the prostate, and the appendix. AggNETs are also prone to occlude the ductal system of exocrine glands, as seen in ocular glands, salivary glands, and others. Last, but not least, they also clog the pancreatic ducts in a murine model of neutrophilia. In this regard, elucidating the mechanism of NETs‐dependent occlusions is of crucial importance for the development of new therapeutic approaches. Therefore, the purpose of this review is to address the putative mechanisms of NETs‐associated occlusions in the pathogenesis of disease, as well as prospective treatment modalities.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Aggregation; Ducts; Neutrophil extracellular traps; Occlusions; Vessels

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

Neutrophil Extracellular Traps Initiate Gallstone Formation - Munoz, Luis Enrique; Boeltz, Sebastian; Bilyy, Rostyslav; Schauer, Christine; Mahajan, Aparna; Widulin, Navena; Grüneboom, Anika; Herrmann, Irmgard; Boada, Edgyda; Rauh, Manfred; Krenn, Veit; Biermann, Mona H.C.; et al. (Immunity, 2019)
The presence of gallstones (cholelithiasis) is a highly prevalent and severe disease and one of the leading causes of hospital admissions worldwide. Due to its substantial health impact, we investigated the biological mechanisms that lead to the formation and growth of gallstones. We show that gallstone assembly essentially requires neutrophil extracellular traps (NETs). We found consistent evidence for the presence of NETs in human and murine gallstones and describe an immune-mediated process requiring activation of the innate immune system for the formation and growth of gallstones. Targeting NET formation via inhibition of peptidyl arginine deiminase type 4 or abrogation of reactive oxygen species (ROS) production, as well as damping of neutrophils by metoprolol, effectively inhibit gallstone formation in vivo. Our results show that after the physicochemical process of crystal formation, NETs foster their assembly into larger aggregates and finally gallstones. These insights provide a feasible therapeutic concept to prevent cholelithiasis in patients at risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: calcium carbonate crystals; cholesterol crystals; gallstone growth; gallstones; lisosomal leakage; lithogenic diet; neutrophil extracellular traps; neutrophils; NOX2; PADi4

Neutrophil Extracellular Traps (NETs) in the Cerebrospinal Fluid Samples from Children and Adults with Central Nervous System Infections - Appelgren, Daniel; Enocsson, Helena; Skogman, Barbro H.; Nordberg, Marika; Perander, Linda; Nyman, Dag; Nyberg, Clara; Knopf, Jasmin; Munoz, Luis Enrique; Sjowall, Christopher; Sjowall, Johanna (Cells, 2020)
Neutrophils operate as part of the innate defence in the skin and may eliminate the Borrelia spirochaete via phagocytosis, oxidative bursts, and hydrolytic enzymes. However, their importance in Lyme neuroborreliosis (LNB) is unclear. Neutrophil extracellular trap (NET) formation, which is associated with the production of reactive oxygen species, involves the extrusion of the neutrophil DNA to form traps that incapacitate bacteria and immobilise viruses. Meanwhile, NET formation has recently been studied in pneumococcal meningitis, the role of NETs in other central nervous system (CNS) infections has previously not been studied. Here, cerebrospinal fluid (CSF) samples from clinically well-characterised children (N = 111) and adults (N = 64) with LNB and other CNS infections were analysed for NETs (DNA/myeloperoxidase complexes) and elastase activity. NETs were detected more frequently in the children than the adults (p = 0.01). NET presence was associated with higher CSF levels of CXCL1 (p < 0.001), CXCL6 (p = 0.007), CXCL8 (p = 0.003), CXCL10 (p < 0.001), MMP-9 (p = 0.002), TNF (p = 0.02), IL-6 (p < 0.001), and IL-17A (p = 0.03). NETs were associated with fever (p = 0.002) and correlated with polynuclear pleocytosis (r(s) = 0.53, p < 0.0001). We show that neutrophil activation and active NET formation occur in the CSF samples of children and adults with CNS infections, mainly caused by Borrelia and neurotropic viruses. The role of NETs in the early phase of viral/bacterial CNS infections warrants further investigation.
CRIS-Team WoS Importer:2020-03-13

Neutrophil Extracellular Traps Open the Pandora's Box in Severe Malaria - Boeltz, Sebastian; Munoz, Luis Enrique; Fuchs, Tobias A.; Herrmann, Martin; Munoz Becerra, Luis (Frontiers in Immunology, 2017)
EVALuna2:13438

Neutrophil Extracellular Traps Promote the Development and Growth of Human Salivary Stones - Schapher, Mirco; Koch, Michael; Weidner, Daniela; Scholz, Michael; Wirtz, Stefan; Mahajan, Aparna; Herrmann, Irmgard; Singh, Jeeshan; Knopf, Jasmin; Leppkes, Moritz; Grüneboom, Anika; Alexiou, Christoph; et al. (Cells, 2020)
Salivary gland stones, or sialoliths, are the most common cause of the obstruction of salivary glands. The mechanism behind the formation of sialoliths has been elusive. Symptomatic sialolithiasis has a prevalence of 0.45% in the general population, is characterized by recurrent painful periprandial swelling of the affected gland, and often results in sialadenitis with the need for surgical intervention. Here, we show by the use of immunohistochemistry, immunofluorescence, computed tomography (CT) scans and reconstructions, special dye techniques, bacterial genotyping, and enzyme activity analyses that neutrophil extracellular traps (NETs) initiate the formation and growth of sialoliths in humans. The deposition of neutrophil granulocyte extracellular DNA around small crystals results in the dense aggregation of the latter, and the subsequent mineralization creates alternating layers of dense mineral, which are predominantly calcium salt deposits and DNA. The further agglomeration and appositional growth of these structures promotes the development of macroscopic sialoliths that finally occlude the efferent ducts of the salivary glands, causing clinical symptoms and salivary gland dysfunction. These findings provide an entirely novel insight into the mechanism of sialolithogenesis, in which an immune system-mediated response essentially participates in the physicochemical process of concrement formation and growth.
CRIS-Team Scopus Importer:2020-10-09
Keywords: lithogenesis; neutrophil extracellular traps; neutrophils; salivary glands; salivary stones; sialadenitis; sialolithiasis; stone development; stone growth

NEUTROPHILS AND NETS AS ORCHESTRATORS OF INFLAMMATORY DISEASES - Hosari, D.; Hosari, Sami; Mahajan, Aparna; Oreski, Leticija; Schoen, J.; Shan, Xiaomei; Singh, Jeeshan; Wang, H.; Yaykasli, Kürsat Oguz; Knopf, Jasmin; Munoz, Luis Enrique; Schauer, Christine; et al. (CLINICAL AND EXPERIMENTAL RHEUMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-09-17

Neutrophils Orchestrate the Periodontal Pocket - Vitkov, Ljubomir; Munoz Becerra, Luis; Schoen, Janina; Knopf, Jasmin; Schauer, Christine; Minnich, Bernd; Herrmann, Martin; Hannig, Matthias (Frontiers in Immunology, 2021)
The subgingival biofilm attached to tooth surfaces triggers and maintains periodontitis. Previously, late-onset periodontitis has been considered a consequence of dysbiosis and a resultant polymicrobial disruption of host homeostasis. However, a multitude of studies did not show “healthy” oral microbiota pattern, but a high diversity depending on culture, diets, regional differences, age, social state etc. These findings relativise the aetiological role of the dysbiosis in periodontitis. Furthermore, many late-onset periodontitis traits cannot be explained by dysbiosis; e.g. age-relatedness, attenuation by anti-ageing therapy, neutrophil hyper-responsiveness, and microbiota shifting by dysregulated immunity, yet point to the crucial role of dysregulated immunity and neutrophils in particular. Furthermore, patients with neutropenia and neutrophil defects inevitably develop early-onset periodontitis. Intra-gingivally injecting lipopolysaccharide (LPS) alone causes an exaggerated neutrophil response sufficient to precipitate experimental periodontitis. Vice versa to the surplus of LPS, the increased neutrophil responsiveness characteristic for late-onset periodontitis can effectuate gingiva damage likewise. The exaggerated neutrophil extracellular trap (NET) response in late-onset periodontitis is blameable for damage of gingival barrier, its penetration by bacteria and pathogen-associated molecular patterns (PAMPs) as well as stimulation of Th17 cells, resulting in further neutrophil activation. This identifies the dysregulated immunity as the main contributor to periodontal disease.
CRIS-Team Scopus Importer:2021-12-17
Keywords: bacterial membrane vesicles; caspase 11; caspase 4; dysbiosis; dysregulated immunity; NET formation; outer membrane vesicles

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix Rius; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

Neutrophils with low production of reactive oxygen species are activated during immune priming and promote development of arthritis - Chen, Tao; Zhou, Zhen; Liu, Yi; Xu, Jiayi; Zhu, Chenxi; Sun, Rui; Hu, Huifang; Liu, Yan; Dai, Lunzhi; Holmdahl, Rikard; Herrmann, Martin; Zhang, Lulu; et al. (Redox Biology, 2024)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease mediated by immune cell dysfunction for which there is no universally effective prevention and treatment strategy. As primary effector cells, neutrophils are important in the inflammatory joint attack during the development of RA. Here, we used single-cell sequencing technology to thoroughly analyze the phenotypic characteristics of bone marrow-derived neutrophils in type II collagen (COL2)-induced arthritis (CIA) models, including mice primed and boosted with COL2. We identified a subpopulation of neutrophils with high expression of neutrophil cytoplasmic factor 1 (NCF1) in primed mice, accompanied by a characteristic reactive oxygen species (ROS) response, and a decrease in Ncf1 expression in boosted mice with the onset of arthritis. Furthermore, we found that after ROS reduction, arthritis occurred in primed mice but was attenuated in boosted mice. This bidirectional effect of ROS suggested a protective role of ROS during immune priming. Mechanistically, we combined functional assays and metabolomics identifying Ncf1-deficient neutrophils with enhanced migration, chemotactic receptor CXCR2 expression, inflammatory cytokine secretion, and Th1/Th17 differentiation. This alteration was mainly due to the metabolic reprogramming of Ncf1-deficient neutrophils from an energy supply pathway dominated by gluconeogenesis to an inflammatory immune pathway associated with the metabolism of histidine, glycine, serine, and threonine signaling, which in turn induced arthritis. In conclusion, we have systematically identified the functional and inflammatory phenotypic characteristics of neutrophils under ROS regulation, which provides a theoretical basis for understanding the pathogenesis of RA, to further improve prevention strategies and identify novel therapeutic targets.
CRIS-Team Scopus Importer:2024-11-08
Keywords: NADPH oxidase 2; Neutrophil cytoplasmic factor 1; Neutrophils; Reactive oxygen species; Rheumatoid arthritis

NOX2 mediates quiescent handling of dead cell remnants in phagocytes - Hahn, Jonas; Euler, Maximilien; Kilgus, Emelie; Kienhöfer, Deborah; Stoof, Julia; Knopf, Jasmin; Hahn, Madelaine; Harrer, Thomas; Hultqvist, Malin; Olofsson, Peter; Mokhir, Andriy; Holmdahl, Rikard; et al. (Redox Biology, 2019)
The phagocyte NADPH oxidase (the NOX2 complex) generates superoxide, the precursor to reactive oxygen species (ROS). ROS possess both antimicrobial and immunoregulatory function. Inactivating mutations in alleles of the NOX2 complex cause chronic granulomatous disease (CGD), characterized by an enhanced susceptibility to infections and autoimmune diseases such as Systemic lupus erythematosus (SLE). The latter is characterized by insufficient removal of dead cells, resulting in an autoimmune response against components of the cell's nucleus when non-cleared apoptotic cells lose their membrane integrity and present autoantigenic molecules in an inflammatory context. Here we aimed to shed light on the role of the NOX2 complex in handling of secondary necrotic cells (SNECs) and associated consequences for inflammation and autoimmunity during lupus. We show that individuals with SLE and CGD display accumulation of SNECs in blood monocytes and neutrophils. In a CGD phenotypic mouse strain (Ncf1** mice) build-up of SNECs in Ly6CHI blood monocytes was connected with a delayed degradation of the phagosomal cargo and accompanied by production of inflammatory mediators. Treatment with H2O2 or activators of ROS-formation reconstituted phagosomal abundance of SNECs to normal levels. Induction of experimental lupus further induced increased antibody-dependent uptake of SNECs into neutrophils. Lupus-primed Ncf1** neutrophils took up more SNECs than wild type neutrophils, whereas SNEC-accumulation in regulatory Ly6C−/LO monocytes was lower in Ncf1**mice. We deduce that the inflammatory rerouting of immune-stimulatory necrotic material into inflammatory phagocyte subsets contributes to the connection between low ROS production by the NOX2 complex and SLE.
CRIS-Team Scopus Importer:2019-08-06

Oligomannose-Rich Membranes of Dying Intestinal Epithelial Cells Promote Host Colonization by Adherent-Invasive E. coli - Dumych, Tetiana; Yamakawa, Nao; Sivignon, Adeline; Garenaux, Estelle; Robakiewicz, Stefania; Coddeville, Bernadette; Bongiovanni, Antonino; Bray, Fabrice; Barnich, Nicolas; Szunerits, Sabine; Slomianny, Christian; Herrmann, Martin; et al. (Frontiers in Microbiology, 2018)
A novel mechanism is revealed by which clinical isolates of adherent-invasive Escherichia coli (AIEC) penetrate into the epithelial cell layer, replicate, and establish biofilms in Crohn's disease. AIEC uses the FimH fimbrial adhesin to bind to oligomannose glycans on the surface of host cells. Oligomannose glycans exposed on early apoptotic cells are the preferred binding targets of AIEC, so apoptotic cells serve as potential entry points for bacteria into the epithelial cell layer. Thereafter, the bacteria propagate laterally in the epithelial intercellular spaces. We demonstrate oligomannosylation at two distinct sites of a glycoprotein receptor for AIEC, carcinoembryonic antigen related cell adhesion molecule 6 (CEACAM6 or CD66c), on human intestinal epithelia. After bacterial binding, FimH interacts with CEACAM6, which then clusters. The presence of the highest-affinity epitope for FimH, oligomannose-5, on CEACAM6 is demonstrated using LC-MS/MS. As mannose-dependent infections are abundant, this mechanism might also be used by other adherent-invasive pathogens.
EVALuna2:213270

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

Oxidative Burst-Dependent NETosis Is Implicated in the Resolution of Necrosis-Associated Sterile Inflammation - Biermann, Mona H. C.; Podolska, Malgorzata; Knopf, Jasmin; Reinwald, Christiane; Weidner, Daniela; Maueröder, Christian; Hahn, Jonas; Kienhoefer, Deborah; Barras, Alexandre; Boukherroub, Rabah; Szunerits, Sabine; Bilyy, Rostyslav; et al. (Frontiers in Immunology, 2016)
Necrosis is associated with a profound inflammatory response. The regulation of necrosis-associated inflammation, particularly the mechanisms responsible for resolution of inflammation is incompletely characterized. Nanoparticles are known to induce plasma membrane damage and necrosis followed by sterile inflammation. We observed that injection of metabolically inert nanodiamonds resulted in paw edema in WT and Ncf1** mice. However, while inflammation quickly resolved in WT mice, it persisted over several weeks in Ncf1** mice indicating failure of resolution of inflammation. Mechanistically, NOX2-dependent reactive oxygen species (ROS) production and formation of neutrophil extracellular traps were essential for the resolution of necrosis-induced inflammation: hence, by evaluating the fate of the particles at the site of inflammation, we observed that Ncf1** mice deficient in NADPH-dependent ROS failed to generate granulation tissue therefore being unable to trap the nanodiamonds. These data suggest that NOX2-dependent NETosis is crucial for preventing the chronification of the inflammatory response to tissue necrosis by forming NETosis-dependent barriers between the necrotic and healthy surrounding tissue.
EVALuna2:13386

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

Programmable Hierarchical Construction of Mixed/Multilayered Polysaccharide Nanocapsules through Simultaneous/Sequential Nanoprecipitation Steps - Yan, Xibo; Ramos, Ricardo Almeida Neves Sampayo; Alcouffe, Pierre; Munoz, Luis Enrique; Bilyy, Rostyslav O.; Ganachaud, François; Bernard, Julien (Biomacromolecules, 2019)
We report here on a one-pot construction of oil-filled hierarchical capsular assemblies using the nanoprecipitation technique. Relying on multicomponent phase diagrams, we show that simultaneous and/or sequential nanoprecipitations involving polymer combinations can be precisely programmed to design a new class of mixed/multilayered multicomponent nanocapsules, with a precise control of the dimensions, shell thickness/composition, and spatial distribution of the building blocks. The simplicity and tunability of this approach are exemplified here with a library of neutral and ionic polysaccharides giving access to a range of functional multilayered nanocarriers of interest for biomedical applications.
CRIS-Team Scopus Importer:2019-10-15

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Receptor-Mediated NETosis on Neutrophils - Chen, Tao; Li, Yanhong; Sun, Rui; Hu, Huifang; Liu, Yi; Herrmann, Martin; Zhao, Yi; Munoz, Luis Enrique (Frontiers in Immunology, 2021)
Neutrophil extracellular traps (NETs), a web-like structures containing chromatin, have a significant role in assisting the capture and killing of microorganisms by neutrophils during infection. The specific engagement of cell-surface receptors by extracellular signaling molecules activates diverse intracellular signaling cascades and regulates neutrophil effector functions, including phagocytosis, reactive oxygen species release, degranulation, and NET formation. However, overproduction of NETs is closely related to the occurrence of inflammation, autoimmune disorders, non-canonical thrombosis and tumor metastasis. Therefore, it is necessary to understand neutrophil activation signals and the subsequent formation of NETs, as well as the related immune regulation. In this review, we provide an overview of the immunoreceptor-mediated regulation of NETosis. The pathways involved in the release of NETs during infection or stimulation by noninfectious substances are discussed in detail. The mechanisms by which neutrophils undergo NETosis help to refine our views on the roles of NETs in immune protection and autoimmune diseases, providing a theoretical basis for research on the immune regulation of NETs.
CRIS-Team Scopus Importer:2021-12-03
Keywords: chemokine receptor; complement receptors; Fc receptors; neutrophil extracellular traps; pattern recognition receptors

Role of guanylate binding protein-1 in vascular defects associated with chronic inflammatory diseases - Hammon, Matthias; Herrmann, Martin; Bleiziffer, Oliver; Pryymachuk, Galyna; Andreoli, Laura; Munoz, Luis Enrique; Amann, Kerstin Ute; Mondini, Michele; Gariglio, Marisa; Airo, Paolo; Schellerer, Vera; Hatzopoulos, Antonis K.; et al. (Journal of Cellular and Molecular Medicine, 2011)
Rheumatic autoimmune disorders are characterized by a sustained pro-inflammatory microenvironment associated with impaired function of endothelial progenitor cells (EPC) and concomitant vascular defects. Guanylate binding protein-1 (GBP-1) is a marker and intracellular regulator of the inhibition of proliferation, migration and invasion of endothelial cells induced by several pro-inflammatory cytokines. In addition, GBP-1 is actively secreted by endothelial cells. In this study, significantly increased levels of GBP-1 were detected in the sera of patients with chronic inflammatory disorders. Accordingly we investigated the function of GBP-1 in EPC. Interestingly, stable expression of GBP-1 in T17b EPC induced premature differentiation of these cells, as indicated by a robust up-regulation of both Flk-1 and von Willebrand factor expression. In addition, GBP-1 inhibited the proliferation and migration of EPC in vitro. We confirmed that GBP-1 inhibited vessel-directed migration of EPC at the tissue level using the rat arterio-venous loop model as a novel quantitative in vivo migration assay. Overall, our findings indicate that GBP-1 contributes to vascular dysfunction in chronic inflammatory diseases by inhibiting EPC angiogenic activity via the induction of premature EPC differentiation. © 2011 The Authors Journal of Cellular and Molecular Medicine © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Endothelial progenitor cells; Guanylate binding protein-1; Inflammation; Rheumatic autoimmune disorders; Rheumatoid arthritis; Systemic lupus erythematosus; Systemic sclerosis

ROS is the boss - Hahn, Jonas; Kienhofer, Deborah; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Maueröder, Christian; Urbonaviciute, Vilma; Munoz, Luis Enrique; Hultqvist, Malin; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; et al. (2017)
EVALuna2:13467

Sialylation of anti-histone immunoglobulin G autoantibodies determines their capabilities to participate in the clearance of late apoptotic cells - Magorivska, I.; Munoz Becerra, Luis; Janko, Christina; Dumych, Tetiana; Rech, J.; Schett, Georg; Nimmerjahn, Falk; Bilyy, R.; Herrmann, Martin (Clinical and Experimental Immunology, 2016)
The Fc portion of immunoglobulin (Ig)G harbours a single glycosylation site. Glycan sialylation is critical for structure and for certain effector functions of IgG. Anti-histone IgG of patients with systemic lupus erythematosus is reportedly responsible for the recruitment of polymorphonuclear cells (PMN) to the clearance of apoptotic cells. Autoantibodies decorating secondary necrotic cells (SNEC) induce proinflammatory responses after activation of blood-borne phagocytes. Analysing the sialylation status of affinity-purified anti-histone IgG in patients with systemic lupus erythematosus (SLE), we demonstrated that the anti-histone IgG was contained preferentially in the non-sialylated fraction. In functional ex-vivo phagocytosis studies, non-sialylated anti-SNEC IgG directed SNEC preferentially into PMN but did not change their cytokine secretion profiles. In contrast, sialylated IgG reduced the phagocytosis by monocytes of SNEC. Moreover, the sialylated anti-SNEC IgG was not simply anti-inflammatory, but switched the cytokine secretion profiles from interleukin (IL)-6/IL-8 to tumour necrosis factor (TNF)-/IL-1. Here we describe how different sialylation statuses of IgG autoantibodies contribute to the complex inflammatory network that regulates chronic inflammation.
Keywords: autoantibodies; IgG; lectin; sialylation; SLE

Sweet but dangerous - the role of immunoglobulin G glycosylation in autoimmunity and inflammation - Biermann, Mona; Griffante, G.; Podolska, Malgorzata; Boeltz, Sebastian; Stürmer, Jörg; Munoz, Luis Enrique; Bilyy, R.; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2016)
Glycosylation is well-known to modulate the functional capabilities of immunoglobulin G (IgG)-mediated cellular and humoral responses. Indeed, highly sialylated and desialylated IgG is endowed with anti- and pro-inflammatory activities, respectively, whereas fully deglycosylated IgG is a rather lame duck, with no effector function besides toxin neutralization. Recently, several studies revealed the impact of different glycosylation patterns on the Fc part and Fab fragment of IgG in several autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Here, we provide a synoptic update summarizing the most important aspects of antibody glycosylation, and the current progress in this field. We also discuss the therapeutic options generated by the modification of the glycosylation of IgG in a potential treatment for chronic inflammatory diseases.
EVALuna2:13284

The effects of Kv1.3 and IKCa1 channel inhibition on cytokine production and calcium influx of T lymphocytes in rheumatoid arthritis and ankylosing spondylitis - Toldi, Gergely; Munoz, Luis Enrique; Herrmann, Martin; Schett, Georg; Balog, Attila; Munoz Becerra, Luis (Immunologic Research, 2016)
Kv1.3 and IKCa1 lymphocyte potassium channels have been implicated as important targets of selective immunomodulation. We compared the alterations in cytokine production upon selective inhibition of Kv1.3 or IKCa1 channels (by MGTX and TRAM, respectively) in healthy donors (HD), RA and AS patients. We also determined calcium influx kinetics and its sensitivity to Kv1.3 and IKCa1 channel inhibition following PHA activation in CD4, Th1, Th2 and CD8 cells as well as monocytes. The application of TRAM resulted in a lower production of TNF-a and IL1-RA in all three study groups. Inhibition by TRAM had contrary effects on the production of IL-1b and IL-5: While their production was increased by PBMCs of RA patients, this effect was not observed in HD and AS PBMCs. While treatment with MGTX resulted in a similar decrease in calcium influx in the CD4 and Th2 subsets across all study groups, TRAM treatment had opposite effects on RA and HD samples: It decreased calcium influx in the Th2 and CD8 subsets in RA, while only Th1 cells were affected in HDs. The effects of IKCa1 channel inhibition are controversial in samples of RA and AS patients, since it shifts the inflammatory balance into the pro-inflammatory direction.
EVALuna2:13123
Keywords: AS; Calcium influx; Cytokine; IKCa1; Kv1.3; RA

The immune reaction against allogeneic necrotic cells is reduced in Annexin A5 knock out mice whose macrophages display an anti-inflammatory phenotype - Frey, Benjamin; Munoz, Luis Enrique; Pausch, Friederike; Sieber, Renate; Franz, Sandra; Brachvogel, Bent; Poschl, Ernst; Schneider, Holm; Roedel, Franz; Sauer, Rolf; Fietkau, Rainer; Herrmann, Martin; et al. (Journal of Cellular and Molecular Medicine, 2009)
Proteins of the annexin family bind to phospholipids in a Ca2+ dependent manner. The exposure of phosphatidylserine (PS) by apoptotic as well as necrotic cells is one major eat-me-signal for macrophages. Annexin A5 (Anx A5) preferentially binds to PS. The availability of Anx A5 knock out (KO) mice allowed us to investigate for the first time if endogenous Anx A5 modulates the immune response towards allogeneic cells. Furthermore, the effect of Anx A5 gene deletion on the phagocytic process as well as on the inflammatory reaction of macrophages was explored. We found that Anx A5 KO mice have a strongly reduced allogeneic cellular immune reaction against primary as well as secondary necrotic cells. In vivo phagocytosis experiments revealed that macrophages of Anx A5 KO mice displayed an increased uptake of necrotic cells. Additionally, an increased secretion of the anti-inflammatory cytokine IL-10 of isolated macrophages of Anx A5 KO mice after contact with necrotic cells was observed. Furthermore, the promoter activity of the Anx A5 gene was enhanced after stimulation of macrophages. The tumour size of an allogeneic tumour regressed faster when endogenous Anx A5 was present. These data demonstrate that endogenous Anx A5 influences the phagocytosis of necrotic cells, modulates the immune response towards allogeneic cells and acts as an inflammatory protein. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Allogeneic cells; Annexin A5; Immune modulation; Inflammation; Macrophages; Phagocytosis; Primary necrosis; Secondary necrosis

The role of dead cell clearance in the etiology and pathogenesis of systemic lupus erythematosus: dendritic cells as potential targets - Biermann, Mona; Veissi, Susan; Maueröder, Christian; Chaurio Gonzalez, Ricardo Alfredo; Berens, Christian; Herrmann, Martin; Munoz Becerra, Luis (Expert Review of Clinical Immunology, 2014)
Overwhelming apoptosis combined with a deficiency in clearing apoptotic cells is thought to be an important etiopathogenic event in the autoimmune disease systemic lupus erythematosus (SLE). Lazy macrophages, complement or DNase I deficiency as well as insufficient natural IgM might be important factors leading to such a clearance deficiency. A defective clearance of apoptotic cells leads to the activation and maturation of plasmacytoid and myeloid dendritic cells (DCs) by material derived from secondary necrotic cells carrying modified autoantigens. This results in the presentation of autoantigens to autoreactive T and B cells in an immunogenic manner, thereby leading to autoantibody production, chronic inflammation and severe tissue damage. Since DC activation and IFN-? production by plasmacytoid dendritic cells play a critical role in the course of SLE pathogenesis, therapeutic intervention to end this vicious cycle might be a promising approach for treating the disease.
EVALuna2:13019

The TH1 phenotype of follicular helper T cells indicates an IFN-?-associated immune dysregulation in patients with CD21low common variable immunodeficiency - Unger, Susanne; Seidl, Maximilian; van Schouwenburg, Pauline; Rakhmanov, Mirzokhid; Bulashevska, Alla; Frede, Natalie; Grimbacher, Bodo; Pfeiffer, Jens; Schrenk, Klaudia; Munoz, Luis Enrique; Hanitsch, Leif; Stumpf, Ina; et al. (Journal of Allergy and Clinical Immunology, 2017)
A subgroup of patients with common variable immunodeficiency (CVID) experience immune dysregulation manifesting as autoimmunity, lymphoproliferation, and organ inflammation and thereby increasing morbidity and mortality. Therefore treatment of these complications demands a deeper comprehension of their cause and pathophysiology.On the basis of the identification of an interferon signature in patients with CVID with secondary complications and a skewed follicular helper T-cell differentiation in defined monogenic immunodeficiencies, we sought to determine the profile of CD4 memory T cells in blood and secondary lymphatic tissues of these patients.We quantified TH1/TH2/TH17 CD4 memory T cells in blood and lymph nodes of patients with CVID using flow cytometry, analyzed their function, and correlated all findings to the burden of immune dysregulation.Patients with CVID with immune dysregulation had a skewed memory CD4 T-cell differentiation toward a CXCR3(+)CCR6(-) TH1 phenotype both in blood and lymph nodes. Consistent with our phenotypic findings, we observed a higher IFN-? production in peripheral CD4 memory T cells and lymph node-derived follicular helper T cells of patients with CVID compared with those of healthy control subjects. Increased IFN-? production was accompanied by a poor germinal center output, an accumulation of T-box transcription factor (T-bet)(+) B cells in lymph nodes, and an accumulation of T-bet(+)CD21(low) B cells in peripheral blood of affected patients.Identification of excessive IFN-? production by blood and lymph node-derived T cells of patients with CVID with immune dysregulation will offer new therapeutic avenues for this subgroup. CD21(low) B cells might serve as a marker of this IFN-?-associated dysregulation.
EVALuna2:13449

To NET or not to NET: current opinions and state of the science regarding the formation of neutrophil extracellular traps - Boeltz, Sebastian; Amini, Poorya; Anders, Hans-Joachim; Andrade, Felipe; Bilyy, Rostyslav; Chatfield, Simon; Cichon, Iwona; Clancy, Danielle M.; Desai, Jyaysi; Dumych, Tetiana; Dwivedi, Nishant; Gordon, Rachael Ann; et al. (Cell Death and Differentiation, 2019)
Since the discovery and definition of neutrophil extracellular traps (NETs) 14 years ago, numerous characteristics and physiological functions of NETs have been uncovered. Nowadays, the field continues to expand and novel mechanisms that orchestrate formation of NETs, their previously unknown properties, and novel implications in disease continue to emerge. The abundance of available data has also led to some confusion in the NET research community due to contradictory results and divergent scientific concepts, such as pro- and anti-inflammatory roles in pathologic conditions, demarcation from other forms of cell death, or the origin of the DNA that forms the NET scaffold. Here, we present prevailing concepts and state of the science in NET-related research and elaborate on open questions and areas of dispute.
CRIS-Team WoS Importer:2019-02-22

Towards a pro-resolving concept in systemic lupus erythematosus - Böltz, Sebastian; Hagen, Melanie; Knopf, Jasmin; Mahajan, Aparna; Schick, Maximilian; Zhao, Yi; Erfurt-Berge, Cornelia; Rech, Jürgen; Munoz Becerra, Luis; Herrmann, Martin (Seminars in Immunopathology, 2019)
Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease with prominent chronic inflammatory aspects. SLE most often affects women (9:1) in childbearing age. The multifactorial nature of the etiopathogenesis of SLE involves a deficient clearance of dead and dying cells. This is supported by the occurrence of autoantibodies directed against autoantigens modified in dying and dead cells (dsDNA, high mobility group box 1 protein, apoptosis-associated chromatin modifications, e.g., histones H3-K27-me3; H2A/H4 AcK8,12,16; and H2B-AcK12) that are deposited in various tissues, including skin, kidneys, joints, muscles, and brain. The subsequent hyperinflammatory response often leads to irreparable tissue damage and organ destruction. In healthy individuals, dead and dying cells are rapidly removed by macrophages in an anti-inflammatory manner, referred to as efferocytosis. In SLE, extensive and prolonged cell death (apoptosis, necrosis, neutrophil extracellular trap (NET) formation) leads to autoantigens leaking out of the not cleared cell debris. These neo-epitopes are subsequently presented to B cells by follicular dendritic cells in the germinal centers of secondary lymphoid tissues conditioning the break of self-tolerance. Activation of autoreactive B cells and subsequent production of autoantibodies facilitate the formation of immune complexes (ICs) fueling the inflammatory response and leading to further tissue damage. ICs may also be ingested by phagocytes, which then produce further pro-inflammatory cytokines. These processes establish a vicious circle that leads to sustained inflammation. This review highlights the cell death–related events in SLE, the protagonists involved in SLE pathogenesis, the resolution of inflammation in various tissues affected in SLE, and explores strategies for intervention to restore hemostasis in a hyperinflammatory state.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Apoptosis; Clearance; Inflammation; Neutrophil extracellular traps (NETs); Resolution; Secondary necrosis; Systemic lupus erythematosus (SLE)

Treatment with DNases rescues hidden neutrophil elastase from aggregated NETs - Podolska, Malgorzata; Mahajan, Aparna; Hahn, Jonas; Knopf, Jasmin; Maueröder, Christian; Petru, Lenka; Ullmann, Marc; Schett, Georg; Leppkes, Moritz; Herrmann, Martin; Munoz, Luis Enrique; Schauer, Christine (Journal of Leukocyte Biology, 2019)
The release of neutrophil extracellular traps (NETs) is one of the weapons neutrophils have in their armory. NETs consist of extracellular chromatin fibers decorated with a plethora of cytoplasmic and granular proteins, such as the antimicrobial serine protease neutrophil elastase (NE). Because the first description of NETs as beneficial to the host, reports on their double-faced role in health and disease have considerably increased recently. On one hand, NETs reportedly trap and kill bacteria and also participate in the resolution of the acute inflammation associated with infection and with tissue damage. On the other hand, numerous negative aspects of NETs contribute to the etiopathogenesis of autoimmune disorders. Employing soluble and solid fluorescent substrates, we demonstrate the interaction of NE with aggregated NETs (aggNETs), the limitation of its enzymatic activity and the containment of the enzyme from surrounding tissues. These events prevent the spread of inflammation and tissue damage. The detection of DNase 1-dependent elevation of NE activity attests the continuous presence of patrolling neutrophils forming NETs and aggNETs even under conditions physiologic conditions.
CRIS-Team Scopus Importer:2019-09-17
Keywords: aggregated NETs; DNase 1; NETs; neutrophil elastase; neutrophils

Tumor immunotherapy: lessons from autoimmunity - Maueröder, Christian; Munoz Becerra, Luis; Chaurio Gonzalez, Ricardo Alfredo; Herrmann, Martin; Schett, Georg; Berens, Christian (Frontiers in Immunology, 2014)
EVALuna2:12986

Unconventional apoptosis of polymorphonuclear neutrophils (PMN): staurosporine delays exposure of phosphatidylserine and prevents phagocytosis by M?-2 macrophages of PMN - Franz, S.; Munoz, Luis Enrique; Heyder, P.; Herrmann, Martin; Schiller, M.; Munoz Becerra, Luis (Clinical and Experimental Immunology, 2015)
Apoptosis of polymorphonuclear neutrophils (PMN) and subsequent 'silent' removal represents an important check-point for the resolution of inflammation. Failure in PMN clearance resulting in secondary necrosis-driven tissue damage has been implicated in conditions of chronic inflammation and autoimmunity. Apoptotic PMN undergo profound biophysical changes that warrant their efficient recognition and uptake by phagocytes before fading to secondary necrosis. In this study, we demonstrate that staurosporine (STS), a non-selective but potent inhibitor of cyclin-dependent kinase and protein kinase C, exerts a drastic impact on PMN apoptosis. PMN treated with STS underwent an unconventional form of cell death characterized by a delayed exposure of aminophospholipids, including phosphatidylserine (PS) and phosphatidylethanolamine and an increased exposure of neo-glycans. STS caused an impaired cellular fragmentation and accelerated DNA fragmentation. Phagocytosis of STS-treated PMN lacking PS on their surfaces was decreased significantly, which highlights the importance of PS for the clearance of apoptotic PMN. Specific opsonization with immune complexes completely restored phagocytosis of STS-treated PMN, demonstrating the efficiency of back-up clearance pathways in the absence of PS exposure.
EVALuna2:13057

Updates on NET formation in health and disease - Leppkes, Moritz; Schick, Maximilian; Hohberger, Bettina; Mahajan, Aparna; Knopf, Jasmin; Schett, Georg; Munoz, Luis Enrique; Herrmann, Martin (Seminars in Arthritis and Rheumatism, 2019)
Following a recent presentation at ATT Mallorca in May 2019, this paper gives insight into the current research of neutrophil extracellular traps (NETs) and their role in conditions of health and disease. Though NETs reportedly support disease progression and play a role in the development of autoimmune diseases, we argue that NETs are mandatory for the mammalian immune system. They are especially important to patrol and surveil outer and inner body surfaces and are capable to perform major anti-microbial activities. Neutrophils are the first cells to be recruited to wounds, where they form NETs and aggregated NETs (aggNETs). The latter close the wounds and are ever-present in skinfolds, where the integrity of the skin is impaired. On infected ocular surfaces NETs form an antimicrobial barrier, which prevents bacterial dissemination into the brain. In the oral cavity, NETs display anti-bacterial properties. Although NETs on internal body surfaces like ducts and vessels offer superficial surveillance, exaggerated aggNET formation may directly block vessels and ducts and thus cause thrombi and ductal occlusion, respectively. In the case of biliopancreatic ducts, clogging by aggNETs may even cause acute pancreatitis. Insufficient clearance of apoptotic remnants and NETs can lead to autoimmune diseases or unwanted, chronic inflammation. To prevent this, macrophages cloak dead cells, while apoptotic cells are cleared. We conclude that neutrophils, NETs and aggNETs can be considered double edged swords that orchestrate the innate immune response but carry the risk to precipitate autoimmunity and epithelial damage.
CRIS-Team Scopus Importer:2019-12-03
Keywords: aggNETs; Apoptosis; Clearance; Ductal occlusion; Innate inflammation; NETs; Thrombi

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

Working with "H2S": Facts and apparent artifacts - Wedmann, Rudolf; Bertlein, Sarah; Macinkovic, Igor; Böltz, Sebastian; Miljkovic, Jan; Munoz Becerra, Luis; Herrmann, Martin; Filipovic, Milos (Nitric Oxide-Biology and Chemistry, 2014)
Hydrogen sulfide (H2S) is an important signaling molecule with physiological endpoints similar to those of nitric oxide (NO). Growing interest in its physiological roles and pharmacological potential has led to large sets of contradictory data. The principle cause of these discrepancies can be the common neglect of some of the basic H2S chemistry. This study investigates how the experimental outcome when working with H2S depends on its source and dose and the methodology employed. We show that commercially available NaHS should be avoided and that traces of metal ions should be removed because these can reduce intramolecular disulfides and change protein structure. Furthermore, high H2S concentrations may lead to a complete inhibition of cell respiration, mitochondrial membrane potential depolarization and superoxide generation, which should be considered when discussing the biological effects observed upon treatment with high concentrations of H2S. In addition, we provide chemical evidence that H2S can directly react with superoxide. H2S is also capable of reducing cytochrome c(3+) with the concomitant formation of superoxide. H2S does not directly react with nitrite but with NO electrodes that detect H2S. In addition, H2S interferes with the Griess reaction and should therefore be removed from the solution by Cd(2+) or Zn(2+) precipitation prior to nitrite quantification. 2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO) is reduced by H2S, and its use should be avoided in combination with H2S. All these constraints must be taken into account when working with H2S to ensure valid data.
EVALuna2:12902